Gas Supply

The sheet laminate with a microporous membrane, gas permeable nonporous layer, and microorganism support layer addresses strength and waterproofness issues, maintaining effective oxygen supply and purification performance in wastewater treatment devices.

JP7612762B2Active Publication Date: 2025-01-14SEKISUI CHEMICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023099395
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-27
Filing Date
2023-06-16
Publication Date
2025-01-14
Estimated Expiration
2039-03-28

AI Technical Summary

Technical Problem

Existing gas permeable membranes in wastewater treatment devices face issues with strength under water pressure, waterproofness due to fabric unevenness, and hydrophilicity leading to impaired air permeability and long-term waterproof properties.

Method used

A sheet laminate comprising a microporous membrane base material, a gas permeable nonporous layer, and a microorganism support layer, laminated in a specific order to ensure adhesiveness and maintain waterproofness while allowing oxygen permeation, with a microbial adhesion index of 0.08 or more and biofilm thickness between 1 to 5 mm.

Benefits of technology

The laminate maintains purification performance by preventing water leakage and ensuring consistent oxygen supply to microorganisms, enhancing wastewater treatment efficiency and longevity of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612762000012
    Figure 0007612762000012
  • Figure 0007612762000013
    Figure 0007612762000013
  • Figure 0007612762000014
    Figure 0007612762000014
Patent Text Reader

Abstract

To provide a sheet stacked body capable of maintaining a cleaning performance of a drainage water treatment apparatus.SOLUTION: A sheet stacked body 21 is used in a drainage water treatment apparatus that cleans drainage water using a function of microorganisms in the drainage water. The sheet stacked body 21 includes a substrate 211 and a gas permeating imperforate layer 212, where the substrate 211 is a fine multi-porous membrane.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sheet laminate used in a wastewater treatment device that purifies wastewater by utilizing the action of microorganisms contained in the wastewater, a method for manufacturing a bag for a gas supplier to be placed in the wastewater treatment device using the sheet laminate, a gas supplier for water treatment having the sheet laminate, a supplier unit in which the gas supplier is unitized, and a wastewater treatment device in which the supplier unit is placed. [Background technology]

[0002] In recent years, wastewater treatment devices have been developed that utilize the action of aerobic microorganisms to decompose organic matter in water and purify wastewater. For example, in these wastewater treatment devices, a gas-permeable membrane that allows gas to pass but not liquid to pass therethrough is used to supply oxygen to the aerobic microorganisms contained in the wastewater. Examples of such gas-permeable membranes are disclosed in Patent Documents 1 and 2.

[0003] Patent Document 1 discloses a gas-permeable membrane formed only from silicone resin, and a gas-permeable membrane in which the surface of a fabric is coated with silicone resin.

[0004] Patent Document 2 discloses a single-layer microporous membrane made of a silicone-based material, which has minute pores with a diameter of less than about 0.5 micrometers. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 3743771 [Patent Document 2] Patent No. 4680504 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the gas-permeable membrane formed only from the silicone resin disclosed in Patent Document 1, it is difficult to ensure the strength to withstand the tensile stress caused by water pressure. In addition, in the gas-permeable membrane in which the surface of the fabric is coated with the silicone resin, the above problems can be avoided, but the unevenness of the fabric causes defects in the resin coating, making it difficult to maintain waterproofness. In addition, if the resin coating is made thicker to maintain waterproofness, the air permeability is impaired.

[0007] Moreover, in the single-layer microporous membrane disclosed in Patent Document 2, the pores of the single-layer microporous membrane become hydrophilic with long-term use, and the membrane is no longer able to maintain its waterproofness.

[0008] The present invention has been made to solve the above problems, and its object is to provide a sheet laminate for use in a wastewater treatment device that purifies wastewater by utilizing the action of microorganisms contained in the wastewater or held on its surface, and that can maintain the purification performance of the wastewater treatment device. Another object of the present invention is to provide a method for manufacturing a bag for a gas supplier to be placed in the wastewater treatment device using the sheet laminate, a gas supplier for water treatment having the sheet laminate, a supplier unit in which the gas supplier is unitized, and a wastewater treatment device in which the supplier unit is placed. [Means for solving the problem]

[0009] In order to achieve the above object, the present invention includes the subject matter described in the following paragraphs.

[0010] Item 1. Used in wastewater treatment equipment that purifies wastewater using the activity of microorganisms in the wastewater. A sheet laminate comprising: A substrate and a gas-permeable non-porous layer, The sheet laminate, wherein the substrate is a microporous membrane.

[0011] Item 2. The sheet laminate according to item 1, further comprising a microbial support layer.

[0012] Item 3. The sheet laminate according to item 2, wherein the gas-permeable non-porous layer has adhesive properties, and the microorganism support layer, the gas-permeable non-porous layer, and the base material are laminated in this order from the side in contact with wastewater, and the surface of the gas-permeable non-porous layer having adhesive properties that contacts the wastewater is the microorganism support layer.

[0013] Item 4. The sheet laminate according to item 2 or 3, characterized in that the sheet laminate has a microbial adhesion index MA calculated by the following formula (1) of 0.08 or more. Formula (1): MA = W × Q2.8 × 10-6 (W: basis weight of microbial support layer (g / m2), Q: oxygen permeability (g / (m2 d)))

[0014] Item 5. The sheet laminate according to any one of Items 2 to 4, wherein the biofilm thickness, as measured under the biofilm evaluation conditions described below, is 1 mm or more and 5 mm or less. (Biofilm evaluation conditions) (1) The sheet stack is placed on one vertical side of a cube with an inner dimension of 7 cm, and the sealed evaluation chamber is filled with organic matter-containing water. (2) (Composition of the above organic matter-containing water) Soluble starch: 0.8 g / L, peptone: 0.084 g / L, yeast extract: 0.4 g / L, urea: 0.052 g / L, CaCl2: 0.055 g / L, KH2PO4: 0.017 g / L, MgSO4·7H2O: 0.001 g / L, KCl: 0.07 g / L, NaHCO3: 0.029 g / L. The solvent was tap water. (3) 5 g of paddy field soil, which is soil containing microorganisms responsible for decomposing organic matter, was added, and the evaluation chamber was placed in a thermostatic chamber maintained at 30 ± 2°C and continuously stirred using a stirrer. Under the conditions under which the evaluation is carried out, the liquid in the evaluation tank is completely discharged every 3.5 days. (4) After the organic matter-containing water was replaced for 28 days, the organic matter-containing water was filled into the evaluation tank (time Ta), and after 3 days (time Tb), the sheet laminate was Here, the mass of the paddy field soil is defined as the mass after centrifuging the aqueous dispersion of the paddy field soil and discarding the supernatant.

[0015] Item 6. The gas-permeable non-porous layer has a basis weight of 10 g / m 2 6. The sheet laminate according to any one of items 1 to 5, wherein:

[0016] Item 7. The sheet laminate according to any one of Items 1 to 6, wherein the gas-permeable non-porous layer is formed from one or more resins selected from the group consisting of urethane resins and silicone resins.

[0017] Item 8. The sheet laminate, The outermost layer is immersed in a liquid so as to come into contact with the liquid, and oxygen is supplied to the inside by allowing the oxygen to permeate to the outside, thereby supplying oxygen to the liquid, The oxygen supply performance to the liquid calculated by the method shown in the oxygen supply test below is 25g / m 2 The sheet laminate according to any one of items 1 to 7, wherein: (Oxygen supply test) Ion-exchanged water having the following (a) is poured into a sealed tank having a cubic shape with sides of 7 cm and one vertical side formed by the sheet laminate, and then an oxygen concentration measurement test is conducted in which the oxygen concentration inside the sealed tank is continuously measured while the ion-exchanged water is stirred by rotating a stirrer rotor. The oxygen supply performance is calculated based on the time-series data of the oxygen concentration measured in the oxygen concentration measurement test. (a) Sodium sulfite is added at a concentration of 100 mg / L and anhydrous cobalt(II) chloride is added at a concentration of 4 mg / L or more.

[0018] Item 9. The sheet laminate, The outermost layer is immersed in a liquid so as to come into contact with the liquid, and oxygen is supplied to the inside by allowing the oxygen to permeate to the outside, thereby supplying oxygen to the liquid, Item 9. The sheet laminate according to any one of items 1 to 8, having a short-term pressure resistance of 0.2 MPa or more.

[0019] Item 10. The sheet laminate, A method for supplying oxygen to wastewater, comprising: 10. The sheet laminate according to any one of items 1 to 9, wherein the number of through-holes in the plate through which water passes is 50 or less under the following water permeability measurement conditions. (Water permeation measurement conditions) A plate material having 813 through holes with a diameter of 3 mm formed in a grid pattern with a pitch of 4 mm is placed opposite the sheet laminate, and a water pressure application test is performed in which a water pressure of 0.02 MPa or more and 1 MPa or less is applied to the sheet laminate for 50 days, and the number of through holes through which water passes is measured.

[0020] Item 11. A method for manufacturing a bag for a gas supplier to be placed in the wastewater treatment device using the sheet laminate according to any one of items 1 to 10, The substrate is made of a thermoplastic resin, A method for producing a bag for a gas supply body, comprising heat-sealing the base materials of one or more of the sheet laminates to form a bag, thereby obtaining the bag.

[0021] Item 12. A gas supply for water treatment comprising a sheet laminate according to any one of claims 1 to 10, comprising one gas transport layer and one or more gas permeable non-porous layers.

[0022] Item 13. A gas supplier according to item 12, characterized in that a leak parameter X represented by the following formula (2) when immersed to an effective sheet height H (m) is 1.9 or more. X=E / (P×A) Equation (2) E: Elastic parameter of gas-permeable impermeable layer (N / 10mm) P: Water pressure applied to the sheet (kPa), expressed by the relationship P = 10 x H, where H (m) is the effective sheet height. A: Diameter of the vent hole on the surface of the gas delivery layer (mm)

[0023] Item 14. A gas supplier unit in which the gas supplier according to item 12 or 13 is unitized.

[0024] Item 15. A wastewater treatment device in which the supplier unit according to item 14 is disposed. Effect of the Invention

[0025] According to the present invention, the sheet laminate contains a substrate that is a microporous membrane and a gas-permeable nonporous layer, so that the purification performance of the wastewater treatment device can be maintained. [Brief description of the drawings]

[0026] [Figure 1] 1 is a vertical sectional view showing a wastewater treatment device according to a first embodiment of the present invention. [Diagram 2] 1 is a horizontal cross-sectional view showing a wastewater treatment device according to a first embodiment of the present invention. [Diagram 3] FIG. 2 is a vertical cross-sectional view showing a wastewater treatment device according to a first embodiment of the present invention, showing a cross section perpendicular to FIG. [Figure 4] FIG. 2 is a vertical cross-sectional view showing a gas supplier disposed in the wastewater treatment device. [Diagram 5] FIG. 5 is a perspective view showing a gas-delivery layer constituting the gas supplier of FIG. 4. [Figure 6] This is a schematic diagram illustrating a microbial aggregate formed on the surface of a sheet laminate of a gas supply body immersed in wastewater in a wastewater treatment tank of the wastewater treatment device of Figure 1, and the decomposition of at least one organic substance or nitrogen source by the microorganisms. [Figure 7] 5 is a flowchart showing a flow of a method for producing the gas supplier of FIG. [Figure 8] FIG. 5 is a schematic diagram showing a process of forming the gas moisture permeable, water impermeable layer constituting the gas supplier of FIG. 4 into a bag shape. [Figure 9] 9 is a schematic diagram showing a process of inserting a hollow plate-like member (corrugated cardboard material) from the opening of the bag-shaped gas-vapor-permeable, water-impermeable layer in FIG. 8. FIG. [Figure 10] FIG. 4 is a cross-sectional view showing the configuration of a gas supplier according to a second embodiment of the present invention. [Figure 11] FIG. 11 is an enlarged view of part A in FIG. [Figure 12] FIG. 2 is an exploded perspective view showing the configuration of a gas-sending layer included in the gas supplier according to the present invention. [Figure 13] FIG. 2 is a perspective view showing a gas delivery layer included in the gas supply according to the present invention. [Figure 14] FIG. 11 is a vertical cross-sectional view showing a gas supplier in embodiment 3. [Figure 15] 1 is a photograph of the sheet laminates of the examples and comparative examples after evaluation of biofilm formation. [Figure 16] 1 is a graph showing the change over time in organic matter removal rate in Examples and Comparative Examples. [Figure 17] FIG. 13 is a plan view of a measuring device used in a water pressure measurement test according to the fifth embodiment. [Figure 18] FIG. 13 is a side view of a measuring device used in a water pressure measurement test according to the fifth embodiment. [Figure 19] FIG. 13 is a cross-sectional view showing an assembled state of a measuring device used in a water pressure measurement test of embodiment 5. [Figure 20] FIG. 13 is a cross-sectional view showing an exploded state of a measuring device used in a water pressure measurement test according to the fifth embodiment. [Figure 21] 13 is a photograph showing a plate material provided in the measuring device of the fifth embodiment. [Figure 22] 13 is a cross-sectional view showing another example of an assembled state of the measuring device used in the water pressure measurement test of embodiment 5. FIG. [Diagram 23] 13 is a photograph showing the state of the plate material and the sponge when the measurement process is performed in the fifth embodiment. [Figure 24] FIG. 13 is a schematic diagram showing a gas supplier of a sixth embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] (Embodiment 1) A sheet laminate according to a first embodiment of the present invention, a gas supplier including the sheet laminate, and a wastewater treatment device in which the gas supplier is disposed will be described with reference to the drawings.

[0028] Fig. 1 is a vertical cross-sectional view showing a wastewater treatment device 50 according to a first embodiment of the present invention. Fig. 2 is a horizontal cross-sectional view showing the wastewater treatment device 50. Fig. 3 is a vertical cross-sectional view showing the wastewater treatment device 50, showing a cross section perpendicular to Fig. 1.

[0029] (Wastewater treatment device 50) The wastewater treatment device 50 of this embodiment utilizes the action of aerobic microorganisms contained in the wastewater W to decompose at least one organic matter or nitrogen source in the wastewater W, thereby purifying the wastewater W. As shown in Figs. 1 to 3, the wastewater treatment device 50 includes a wastewater treatment tank 51, a supply unit 52, and a gas supply source 53 (see Fig. 1).

[0030] (Wastewater treatment tank 51) As shown in FIGS. 1 to 3, the wastewater treatment tank 51 is a bottomed container in which wastewater W is stored, and is provided with an inlet 51a and an outlet 51b on opposing side surfaces.

[0031] In this embodiment, the inlet 51a and the outlet 51b are always open. The wastewater W is continuously or intermittently supplied from the inlet 51a to the outlet 51b disposed opposite the inlet 51a (arrows in FIG. 3 indicate the flow of the wastewater W).

[0032] The volume of the wastewater treatment tank 51 is not particularly limited, but may be, for example, 1 m 3 More than 10,000m 3 The following volume is sufficient:

[0033] (Supplier Unit 52) 1, the supplier unit 52 is a unitized gas supplier 10, and is disposed inside the wastewater treatment tank 51. In the illustrated example, the supplier unit 52 is composed of a plurality of gas suppliers 10 arranged in parallel. The supplier unit 52 is disposed so that each gas supplier 10 except for its upper end portion is immersed in the wastewater W during use.

[0034] (Gas supplier 10) Each gas supplier 10 constituting the supplier unit 52 is a structure that supplies gas supplied from the opening 21b into the wastewater W in a state immersed in the wastewater W of the wastewater treatment tank 51. The gas supplied into the wastewater W through the gas supplier 10 is preferably a gas containing oxygen in order to promote activation of aerobic microorganisms in the wastewater W. Specifically, it may be air or pure oxygen. In the illustrated example, gas is supplied from a gas supply source 53 to the opening 21b, and an air supply device or the like can be used as the gas supply source 53. From the viewpoint of keeping manufacturing costs low, air in the atmosphere may be directly introduced into the gas supplier 10 from the opening 21b without using the gas supply source 53.

[0035] As shown in Fig. 2 and Fig. 3, each gas supplier 10 is a flat plate-like member and is arranged so that its surface extends in the vertical direction (depth direction) and the lateral direction (horizontal direction). This ensures an efficient contact area with the wastewater W. Also, by arranging each gas supplier 10 so that its side surface is parallel to a straight line connecting the inlet 51a and the outlet 51b, the wastewater W supplied from the inlet 51a into the wastewater treatment tank 51 flows smoothly toward the outlet 51b. The number of gas suppliers 10 constituting the supplier unit 52 does not necessarily need to be plural, and may be singular.

[0036] If the interval between the gas suppliers 10 is defined as "the interval between the outer surfaces of two adjacent gas suppliers 10, not including the thickness of the gas suppliers 10," the interval between the gas suppliers 10 is preferably 5 mm or more and 200 mm or less. If the interval between the gas suppliers 10 is less than 5 mm, clogging may occur due to microorganisms growing on the sheet laminate 21. If the interval between the gas suppliers 10 exceeds 200 mm, the contact efficiency with the wastewater may deteriorate, making it difficult to improve the wastewater treatment performance. In order to reliably avoid the above problems, it is more preferable to set the interval between the gas suppliers 10 to 15 mm or more and 50 mm or less.

[0037] FIG. 4 is a vertical cross-sectional view of the gas supply body 10. As shown in FIG. 4, the gas supply body 10 includes a gas-delivery layer 12 and a sheet laminate 21, and the gas-delivery layer 12 is disposed in a bag formed by the sheet laminate 21. The bag is formed by overlapping two sheet laminates 21, 21 and bonding three ends of the sheet laminates 21, 21, and has an opening 21b (see FIG. 4) at the upper end (the end of the gas-delivery layer 12 on the gas supply side). The gas-delivery layer 12 is inserted into the bag through the opening 21b, so that the outer periphery of the gas-delivery layer 12 is covered by the sheet laminate 21. The position or shape of the opening 21b is not limited, and for example, a part of each end (including the top side, bottom side, and horizontal side (vertical line) of the bag) may be an opening.

[0038] (Gas delivery layer 12) FIG. 5 is a perspective view showing the gas-delivery layer 12. The gas-delivery layer 12 is a hollow plate-like member made of paper, resin, or metal. The gas-delivery layer 12 is a structure having a gas flow path S that delivers gas supplied from a first end along a first direction. Gas from a gas supply source 53 (FIG. 1) or air in the vicinity of the opening 21b is supplied to the upper end of the gas-delivery layer 12 (the end of the gas-delivery layer 12 on the gas supply side) through the opening 21b (FIG. 4). The gas-delivery layer 12 has a gas flow path S that delivers gas supplied to the upper end in the first direction (see the two-dot chain line in FIG. 5), and releases the gas from the gas passing holes 13 on the side.

[0039] 5, the gas-delivery layer 12 has a plurality of cores 12a, a front liner 12b, and a back liner 12c. The front and back surfaces of the gas-delivery layer 12 are formed by the front liner 12b and the back liner 12c, which are plate-shaped members.

[0040] The core materials 12a each extend in a first direction and are arranged at a predetermined interval in a direction perpendicular to the first direction. The core materials 12a are sandwiched between the front liner 12b and the rear liner 12c, so that a plurality of gas flow paths S partitioned by the core materials 12a are formed in the space between the front liner 12b and the rear liner 12c.

[0041] Furthermore, when pressed from the front liner 12b and the back liner 12c, each core 12a functions as a support portion that supports the gas supplier 10 so that the space between the front liner 12b and the back liner 12c does not shrink. When the gas supplier 10 is immersed in the wastewater W as shown in Figs. 1 to 3, the core 12a maintains the space between the front liner 12b and the back liner 12c so that the cross-sectional area of ​​the gas flow path S does not shrink due to water pressure. This ensures a sufficient amount of gas delivery in the gas delivery layer 12 (gas flow path S).

[0042] The front liner 12b and the back liner 12c each have a plurality of gas passage holes 13. The gas passage holes 13 are through-holes formed in the front liner 12b and the back liner 12c, and the gas passage holes 13 communicate the gas flow path S with the sheet laminate 21, so that the gas flowing through the gas flow path S is supplied into the liquid via the sheet laminate 21.

[0043] For example, the gas passage holes 13 may be formed when the gas-delivery layer 12 is molded. Alternatively, the gas passage holes 13 may be formed by processing the front liner 12b and the back liner 12c after the gas-delivery layer 12 is molded. The front liner and the back liner may be made of a porous sheet. If sufficient gas supply performance is obtained, the gas-delivery layer may be made of a porous sheet.

[0044] Examples of materials that may be used for the components constituting the gas-sending layer 12 include paper, ceramics, aluminum, iron, and plastics (polyolefin resin, polystyrene resin, polyester resin, polyvinyl chloride resin, acrylic resin, urethane resin, epoxy resin, polyamide resin, methyl cellulose resin, ethyl cellulose resin, polyvinyl alcohol resin, vinyl acetate resin, phenolic resin, fluororesin, and polyvinyl butyral resin).

[0045] In addition, because of their excellent strength, the material of the gas-sending layer 12 is preferably paper, aluminum, iron, polyolefin resin, polystyrene resin, PVC resin, or polyester resin.

[0046] From the viewpoint of keeping material costs low, it is preferable to use, for example, paper, resins such as polyolefin, polystyrene, PVC and polyester, metals such as aluminum, etc. as the material for the gas-delivery layer 12. The material cost for the gas-delivery layer 12 can also be kept low by using, as the gas-delivery layer 12, cardboard formed so that the gas flow path S extends in the first direction (see the two-dot chain line in FIG. 5).

[0047] The pore shape forming the gas permeable pores of the gas-transporting layer 12 can be various pore shapes such as a circle, a polygon (including a honeycomb structure), etc. The pore shape is not particularly limited, but a polygon is preferable, and specifically, a rectangle or a square is preferable.

[0048] In order to maintain the activity of the aerobic microorganisms, it is preferable to maintain the oxygen concentration inside the gas-sending layer 12. For example, a predetermined amount of pure oxygen is supplied to maintain the oxygen concentration constant. For example, a method of supplying the pure oxygen may be a powered air supply.

[0049] Here, the length of the gas flow passage S formed in the gas delivery layer 12 in the vertical direction (depth direction when immersed) may be, for example, 0.2 m or more, preferably 0.8 m or more, or 3.7 m or more. The length may be, for example, 6 m or less, preferably 4 m or less. The length of the gas flow passage S in the horizontal direction perpendicular to the vertical direction may be, for example, 0.2 m or more, preferably 0.4 m or more, or, for example, 3.6 m or less, preferably 1.8 m or less.

[0050] Here, it is preferable that the vertical length of the gas flow path S is equal to or greater than the above-mentioned lower limit value, in that this makes it easier to maintain the gas flow path S and to ventilate the gas flow path S, thereby improving the wastewater treatment capacity, and it is preferable that the vertical length is equal to or less than the above-mentioned upper limit value, in that this makes it easier to obtain the effect of improving the wastewater treatment capacity by ventilating the gas flow path S, and in that it is easier to install.

[0051] In addition, it is preferable for the lateral length of the gas flow path S to be equal to or greater than the above-mentioned lower limit value in order to efficiently secure the contact area with the wastewater W and improve the wastewater treatment efficiency, and it is preferable for the lateral length of the gas flow path S to be equal to or less than the above-mentioned upper limit value in order to easily maintain the strength of the entire gas supplier 10 and to easily install the supplier unit 52.

[0052] The ratio of the length Lw of contact with the wastewater W to the length Ls of the gas flow path S may be, for example, 80% or more and 95% or less (see FIG. 1 for lengths Ls and Lw). It is preferable that the ratio of the length Lw of contact with the wastewater W to the length Ls is equal to or more than the lower limit, in order to ensure a good amount of oxygen supplied from the gas flow path S and improve the efficiency of wastewater treatment. It is preferable that the ratio of the length Lw of contact with the wastewater W to the length Ls is equal to or less than the upper limit, in order to prevent the wastewater W from entering the gas flow path S.

[0053] Alternatively, in order to prevent the waste water W from entering the gas flow path S, the water contact length Lw may be set so that the water surface of the waste water W is 2 cm or more away from the opening 21b of the gas supplier 10 (sheet laminate 21).

[0054] (Sheet laminate 21) The sheet laminate 21, in a state where the outermost layer is immersed in the liquid (wastewater) so as to contact the liquid (wastewater), allows oxygen supplied to the inside (gas-sending layer 12 side) to permeate outward, thereby supplying oxygen into the liquid (wastewater). When the gas supplier 10 is immersed in the wastewater treatment tank 51, the sheet laminate 21 has a property of allowing air to permeate from the inside (gas-sending layer 12) to the outside (wastewater W) and not allowing wastewater to permeate from the outside (wastewater W) to the inside (gas-sending layer 12). As a result, aerobic microorganisms in the wastewater W gather on the surface 21a of the sheet laminate 21 to which air (oxygen) is continuously supplied, as shown in FIG. 6. Therefore, microorganisms attach to the surface 21a of the sheet laminate 21, forming a biofilm 214. Then, due to the action of the microorganisms contained in the wastewater W or held on the surface 21a, minute solid organic matter or nitrogen compounds dissolved or dispersed in the water are decomposed, and the wastewater is purified.

[0055] Specifically, as shown in FIG. 4, the sheet laminate 21 includes a base material 211, a gas-permeable non-porous layer 212, and a microorganism support layer 213. In the illustrated example, the sheet laminate 21 is laminated in the order of the microorganism support layer 213, the base material 211, and the gas-permeable non-porous layer 212, and the base material 211 is covered with the gas-permeable non-porous layer 212, and the outermost layer that contacts the wastewater W is composed of the microorganism support layer 213. Unlike the illustrated example, the sheet laminate 21 may be laminated in the order of the base material 211, the gas-permeable non-porous layer 212, and the microorganism support layer 213 (opposite to the illustrated example, the base material 211 may be located inside the gas-permeable non-porous layer 212). Even in this way, the base material 211 can be covered with the gas-permeable non-porous layer 212, and the outermost layer that contacts the wastewater W can be composed of the microorganism support layer 213.

[0056] (Base material 211) The substrate 211 is a microporous film made of a thermoplastic resin. The microporous film is a film having a large number of fine through holes. The material of the substrate 211 may include a polymer material selected from fluororesins including polyolefin, polystyrene, polysulfone, polyethersulfone, polyarylsulfone, polymethylpentene, polytetrafluoroethylene, and polyvinylidene fluoride, silicone-based polymers including polybutadiene and poly(dimethylsiloxane), and copolymers of these materials.

[0057] The method for producing the substrate 211, which is a microporous membrane, is not particularly limited, but the substrate 211 can be produced by, for example, a phase separation method, a stretching hole-opening method, a melting recrystallization method, a powder sintering method, a foaming method, or a solvent extraction. The substrate 211 may also be a self-assembled honeycomb microporous membrane.

[0058] The thickness of the substrate 211 is preferably 10 um to 500 um, and more preferably 50 um to 200 um. The thickness of the substrate 211 is measured according to JIS1913:2010 General Nonwoven Fabric Test Method 6.1 Thickness Measurement Method This is the value measured.

[0059] The pore size of the substrate 211 is preferably 0.01 um to 50 um from the viewpoint of preventing defects in the gas-permeable non-porous layer, and is preferably 0.1 um to 30 um from the viewpoint of maintaining high strength and gas permeability. It is more preferable that the pore size is determined by observing the surface with a scanning electron microscope (SEM). The pore diameter was determined from the observed image by the method described below. The observation magnification can be any magnification that allows the pore diameter of the object to be observed to be calculated appropriately. (Method of determining pore size) The images obtained by SEM observation are binarized and the pore diameter is calculated by image analysis. When calculating, the pore diameter is approximated by an ellipse, the length of the major axis of the ellipse is regarded as the pore diameter, and the average value is evaluated.

[0060] Alternatively, the pore size of the substrate 211 is defined as the average pore size obtained from pore size distribution measurement (perm porosimetry) by capillary condensation method. In perm porosimetry, the relationship between the differential pressure between atmospheric pressure and the measured pressure and the gas permeation flow rate is obtained from the gas permeation flow rate measured while gradually increasing the measured pressure of the gas applied to the sample. To obtain the pore size, a wet curve is measured on a wet sample after the sample is immersed in a wetting liquid with a known surface tension, and a dry curve is measured on a dried sample. By gradually increasing the pressure in each case within a predetermined pressure range, information on the through pore size in the sample can be obtained. The average pore size is obtained by finding the point X where the wet curve and a curve with a slope of 1 / 2 that of the dry curve (half dry curve) intersect, and substituting this into the equation, d=2860×γ / DP. In the above equation, d is the average pore size (mm), γ is the surface tension of the wetting liquid (dynes / cm), and DP is the differential pressure (Pa) between the atmospheric pressure and the gas pressure at point X. The measurement is A palm porometer (CFP-1500-AEC) manufactured by Materials Co., Ltd. can be used. The test conditions are, for example, test temperature at room temperature (20°C ± 5°C), wetting liquid G alwick (surface tension 15.7 dynes / cm), compressed air as pressurized gas, 33 mm diameter of sample used, maximum supply pressure 250 psi, differential pressure rise rate 4 psi / min. When preparing a wet sample, the sample can be sufficiently wetted by placing the wetting liquid in which the sample is immersed in a desiccator and degassing it.

[0061] (Gas-permeable non-porous layer 212) The gas-permeable non-porous layer 212 is a layer that has pores with a smaller pore diameter than the pores of the substrate, or has pores with an undetectable diameter and is gas permeable. The pore diameter of the gas-permeable non-porous layer 212 can be measured in the same manner as the pore diameter of the substrate 211.

[0062] Examples of the gas that permeates the gas-permeable non-porous layer 212 include oxygen, carbon dioxide, nitrogen, hydrogen, alcohols such as methanol and ethanol, organic solvents, and mixed gases thereof. From the viewpoint of effectively growing and activating microorganisms, the gas is preferably oxygen or a mixed gas containing oxygen. Gas permeability can be measured by a method specified in JIS K 7126.

[0063] The gas-permeable non-porous layer 212 may be a thermoplastic resin or a thermosetting resin. The thermosetting resin may be a resin that cures by heat or by irradiation with ultraviolet light. It may also be a resin that cures by organic peroxide crosslinking, addition reaction crosslinking, or condensation crosslinking.

[0064] The material of the gas-permeable non-porous layer 212 may include a thermosetting polymer selected from polyolefin, polystyrene, polysulfone, polyethersulfone polytetrafluoroethylene, acrylic resin, polyurethane resin, and copolymers of these materials. Also, a silicone-based silicone resin such as poly(dimethylsiloxane) having a siloxane skeleton of (Si-O-Si)n (n=integer) can be used. Among these, it is particularly preferable to use a urethane resin or a silicone resin.

[0065] Examples of the polyurethane resin that can be used include "Asaflex 825" (manufactured by Asahi Kasei Corporation), "Pellethene 2363-80A", "Pellethene 2363-80AE", "Pellethene 2363-90A", and "Pellethene 2363-90AE" (all manufactured by The Dow Chemical Company), and "Heimullen Y-237NS" (manufactured by Dainichiseika Color & Chemicals Co., Ltd.).

[0066] The silicone resin or silicone polymer, or the silicone resin composition for obtaining them, may be blended or composed without any particular limitation. The monomer used in the silicone resin composition may be monofunctional, difunctional, trifunctional, or tetrafunctional, and may be used alone or in combination of two or more kinds. The monomer may be a halogenated alkylsilane, an unsaturated silane, an aminosilane, a mercaptosilane, or an epoxysilane. Examples of the monomer that may be used include monomers represented by the following chemical formulas: HSiCl3, SiCl4, MeSiHCl2, Me3SiCl, MeSiCl3, Me2SiCl2, Me2HSiCl, PhSiCl3, Ph2SiCl2, MePhSiCl2, Ph2MeSiCl, CH2=CHSiCl3, Me(CH2=CH)SiCl2, Me2(CH2=CH)SiCl, (CF3CH2CH2)MeSiCl 2、 (CF3CH2CH2)SiCl3, CH 18 H 37 SiCl3 (in the chemical formula, "=" represents a double bond, "Me" represents a methyl group, and "Ph" represents a phenyl group). The monomers may be used alone or in combination of two or more. As other organic groups, alkyl groups such as propyl, isopropyl, butyl, isobutyl, tert-butyl, hexyl, octyl, and decyl groups; aryl groups such as phenyl, tolyl, xylyl, and naphthyl groups; cycloalkyl groups such as cyclopentyl and cyclohexyl groups; and aralkyl groups such as benzyl, 2-phenylethyl, and 3-phenylpropyl groups may be used. Among these, methyl groups, phenyl groups, or a combination of both are preferred. Methyl groups, phenyl groups, or a combination of both are preferred. This is because the component is easy to synthesize and has good chemical stability. In addition, when using a polyorganosiloxane with particularly good solvent resistance, it is preferable that the polyorganosiloxane is further a combination of a methyl group, a phenyl group, or a combination of both of them and a 3,3,3-trifluoropropyl group. In addition, the silicone resin composition may contain an organoalkoxysilane. Examples of the organoalkoxysilane include compounds represented by the following chemical formulas, which may be used alone or in combination of two or more types. Me3SiOCH3, Me2Si(OCH3)2, MeSi(OCH3)3, Si(OCH3)4, Me(C2H5)Si(OCH3)2, C2H5Si(OCH3)3, C 10 H 21 Si(OCH3)3, PhSi(OCH3)3, Ph2Si(OCH3)2, MeSiOC2H5, Me2Si(OC2H5)2, Si(OC2H5)4, C2H5Si(OC2H5)3, PhSi(OC2H5)3, Ph2Si(OC2H5)2. Furthermore, the silicone resin composition may contain an organosilanol. Examples of the organosilanol include compounds represented by the following chemical formulas, which may be used alone or in combination of two or more: Me3SiOH, Me2Si(OH)2, MePhSi(OH)2, (C2H5)3SiOH, Ph2Si(OH)2, and Ph3SiOH.

[0067] The reaction method for obtaining the silicone polymer used in the silicone resin may include, for example, hydrolysis of chlorosilane, ring-opening polymerization of cyclic dimethylsiloxane oligomer, etc. Examples of the polymer to be used include dimethyl polymers, methylvinyl polymers, methylphenylvinyl polymers, methylfluoroalkyl polymers, etc.

[0068] The method of curing the silicone polymer, that is, the method of reacting (vulcanizing) to obtain a silicone resin, is not particularly limited. Heat vulcanization or room temperature vulcanization may be used. Either a millable type silicone resin composition or a liquid rubber type silicone resin composition may be used as the state before the reaction. A polymer having a degree of polymerization of about 4000 to 10000 is preferably used as the polymer used in the millable type silicone resin composition. In addition, it may be a one-liquid type or a two-liquid type. As the reaction method, for example, a dehydration condensation reaction between silanol groups (Si-OH), a condensation reaction between a silanol group and a hydrolyzable group, a reaction of a methylsilyl group (Si-CH3) or a vinylsilyl group (Si-CH=CH2) with an organic peroxide, an addition reaction between a vinylsilyl group and a hydrosilyl group (Si-H), a reaction with ultraviolet light, a reaction with an electron beam, etc. may be used.

[0069] (Dehydration condensation reaction between silanol groups) As the catalyst, zinc octylate, iron octylate, or an organic acid salt of cobalt, tin, or the like, or an amine catalyst may be used, and the reaction may be caused to proceed by heating.

[0070] (Condensation reaction between silanol groups and hydrolyzable groups) As a catalyst, an acid, an alkali, an organic tin compound, an organic titanium compound, etc. may be added. As a hydrolyzable group, an alkoxy group, an acetoxy group, an oxime group, an aminoxy group, a propenoxy group, etc. may be used.

[0071] (Reaction of methylsilyl and vinylsilyl groups with organic peroxides) As a peroxide curing agent for accelerating the reaction, an organic peroxide, an acyl-based organic peroxide, an alkyl-based organic peroxide, or the like may be added. As an acyl-based organic peroxide, for example, p-methylbenzoyl peroxide, or the like may be used. As an alkyl-based organic peroxide, for example, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, dicumyl peroxide, or the like may be used. The reaction temperature is, for example, 120°C or higher, and secondary vulcanization (post-cure) may be performed. The amount of peroxide curing agent added is preferably 0.1 to 10% by mass based on the solid content of the resin.

[0072] (Addition reaction of alkenyl group with hydrosilyl group) As the alkenyl group, for example, a vinyl group is preferably used. The reaction temperature may be room temperature or may be heated. The reaction may be carried out in an open system or a closed system. In the process of obtaining a composition used in the addition reaction of an alkenyl group with a hydrosilyl group, an organic compound containing nitrogen, phosphorus, sulfur, etc., an ionic compound of a metal such as tin or lead, a compound having an unsaturated group such as acetylene, an additive for removing alcohol, water, or carboxylic acid may be added or a process of removing the additive may be used.

[0073] When an addition reaction between an alkenyl group and a hydrosilyl group is used, polysiloxanes or hydrogen polysiloxanes having vinyl groups are preferably used.

[0074] The polysiloxane having a vinyl group is preferably a linear polysiloxane having a viscosity of 1 to 100,000 mPa·s at 23° C. The polysiloxane contains one or more vinyl groups in one molecule. Specific examples of polysiloxanes having vinyl groups include dimethylsiloxane-methylvinylsiloxane copolymers capped with trimethylsiloxy groups at both molecular chain ends, methylvinylpolysiloxane capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped with trimethylsiloxy groups at both molecular chain ends, dimethylpolysiloxane capped with dimethylvinylsiloxy groups at both molecular chain ends, methylvinylpolysiloxane capped with dimethylvinylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylvinylsiloxane copolymers capped with dimethylvinylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped with dimethylvinylsiloxy groups at both molecular chain ends, dimethylpolysiloxane capped with trivinylsiloxy groups at both molecular chain ends, etc. These polysiloxanes may be used alone or in combination of two or more.

[0075] The hydrogen polysiloxane is preferably a linear polysiloxane having a viscosity of 1 to 100,000 mPa·s at 23° C. The hydrogen polysiloxane contains one or more hydrogen atoms bonded to silicon atoms in one molecule. Specific examples of hydrogenpolysiloxanes, so long as they have a viscosity at 23°C of 1 to 100,000 mPa·s, include dimethylpolysiloxanes capped at both molecular chain terminals with dimethylhydrogensiloxy groups, dimethylpolysiloxanes capped at both molecular chain terminals with diphenylhydrogensiloxy groups, methylphenylpolysiloxanes capped at both molecular chain terminals with dimethylhydrogensiloxy groups, diphenylpolysiloxanes capped at both molecular chain terminals with dimethylhydrogensiloxy groups, methylphenylsiloxane-dimethylsiloxane copolymers capped at both molecular chain terminals with dimethylhydrogensiloxy groups, diphenylsiloxane-dimethylsiloxane copolymers capped at both molecular chain terminals with dimethylhydrogensiloxy groups, and mixtures of two or more of these.

[0076] In the resin composition used in the addition reaction between alkenyl groups and hydrosilyl groups, the molar ratio of hydrogen atoms bonded to silicon atoms to alkenyl groups is preferably 0.01 to 20 mol, more preferably 1 to 2 mol.

[0077] As the reaction catalyst, for example, platinum group metals such as platinum, palladium, and rhodium can be used, and platinum compounds such as chloroplatinic acid, alcohol-modified chloroplatinic acid, and coordination compounds of chloroplatinic acid with olefins, vinylsiloxane, or acetylene compounds, platinum group metal compounds such as tetrakis(triphenylphosphine)palladium, chlorotris(triphenylphosphine)rhodium, etc. can be used. In addition, since compatibility with silicone oil is required, platinum compounds obtained by modifying chloroplatinic acid with silicone are preferably used. When using a catalyst, the amount of addition calculated from the solid content mass is preferably 0.01 ppm to 10,000 ppm, and more preferably 0.1 ppm to 1,000 ppm.

[0078] The total amount of hydrosilyl groups is usually 0.01 to 20 moles, preferably 0.1 to 10 moles, per mole of alkenyl groups bonded to silicon atoms in the entire silicone resin composition. If the total amount is less than the lower limit of the above range, the resulting silicone resin composition tends to be difficult to cure sufficiently, and if it exceeds the upper limit of the above range, the mechanical properties and heat resistance of the cured product of the resulting silicone resin composition tend to be easily reduced.

[0079] Reaction inhibitors are added to prevent thickening or gelation before curing when silicone resins are mixed or when they are applied to a substrate, etc. Examples of reaction inhibitors include low molecular weight polysiloxanes with multiple alkenyl groups and acetylene alcohol-based compounds.

[0080] (Reaction caused by ultraviolet light) Examples of ultraviolet-curable silicone resins that can be used include radical reaction types (acrylic and mercapto types), combined radical reaction / condensation reaction types (mercapto / isopropenoxy and acrylic / alkoxy types), and addition reaction types that use an ultraviolet-active platinum catalyst.

[0081] In the acrylic radical reaction type, an organic group having an acrylic group bonded to a siloxane is subjected to a radical polymerization reaction in the presence of a photosensitizer.

[0082] In the mercapto-type radical reaction type, an organic group having a mercapto group bonded to a siloxane and a polysiloxane having a vinyl group are subjected to a radical addition reaction in the presence of a photosensitizer.

[0083] Examples of catalysts used in addition reaction types that use ultraviolet-active platinum catalysts include (methylcyclopentadienyl)trimethylplatinum complex and bisacetylacetonatoplatinum(II) complex, and it is suitable for curing with a light source centered around 365 nm.

[0084] The main functional group used in the photocuring reaction may be an acrylic group or an epoxy group. A photoinitiator may be used in the composition used in the reaction by ultraviolet light.

[0085] (Method of imparting tackiness (adhesiveness) to silicone resin) As a method for imparting tackiness (adhesiveness) to a silicone resin, for example, a method of adding a silicone polymer that imparts tackiness is preferably used. As a silicone polymer that imparts tackiness, for example, an MQ resin is preferably used. An MQ resin is a polymer having a three-dimensional structure synthesized from a monofunctional monomer (M unit) and a tetrafunctional monomer (Q unit). The molecular weight of the polymer having the three-dimensional structure is preferably 10 to 100,000, more preferably 100 to 10,000. As the organic group of the monomer of each functional group, a methyl group is preferably used, but in the case of an addition reaction type silicone resin, an alkenyl group is preferably used. The content of the MQ resin relative to the silicone resin is preferably 10 to 99 mass% in terms of solid content, more preferably 20 to 80 mass%, from the viewpoint of achieving both strength and tackiness of the silicone resin. In the present invention, when obtaining a silicone polymer that imparts adhesiveness, a difunctional monomer (D unit) or a trifunctional monomer (T unit) may be added as appropriate, or a monomer or oligomer having other functional groups may be added.

[0086] The MQ resin preferably has a structure in which the ends of a condensation product of Q units are blocked with M units. From the viewpoint of achieving both adhesiveness and strength of the silicone resin, the molar ratio of M units to Q units is preferably 0.4 to 1.2, and more preferably 0.6 to 0.9.

[0087] Additives may be added during the process of obtaining silicone polymers and silicone resins from silicone monomers. Examples of additives include reinforcing agents (silica fillers such as dry silica and wet silica) etc.), dispersants, adhesion aids (silane coupling agents etc.), adhesion promoters (organometallic compounds etc.), reaction control agents, extenders (crystalline silica, calcium carbonate, talc etc.), heat resistance improvers (iron oxide, cerium oxide, titanium oxide etc.), flame retardants (titanium oxide, carbon etc.), thermally conductive fillers, conductive agents, surface treatment agents, pigments, dyes, or metal oxides, hydroxides, carbonates and fatty acid salts of rare earths, titanium, zircon, manganese, iron, cobalt, nickel etc.

[0088] As the silica filler, for example, a known fine powder silica can be used. The fine powder silica may be hydrophilic or hydrophobic. Examples of the hydrophilic fine powder silica include wet silica such as precipitated silica, and dry silica such as silica xerogel and fumed silica. Examples of the hydrophobic fine powder silica include fine powder silica obtained by hydrophobizing the surface of hydrophilic fine powder silica. Examples of the hydrophobizing agent include organosilazanes such as hexamethyldisilazane; halogenated silanes such as methyltrichlorosilane, dimethyldichlorosilane, and trimethylchlorosilane; and organoalkoxysilanes in which the halogen atom of the halogenated silane is substituted with an alkoxy group such as a methoxy group or an ethoxy group. Examples of the hydrophobizing method include a method in which hydrophilic fine powder silica is heat-treated with a hydrophobizing agent at 150 to 200°C, particularly at 150 to 180°C, for about 2 to 4 hours. The hydrophobic fine powdered silica obtained by previously hydrophobizing the surface of the hydrophilic fine powdered silica in this manner may be blended into the adhesive of the present invention, or a hydrophobizing agent may be blended into the adhesive of the present invention together with the hydrophilic fine powdered silica, so that the surface of the hydrophilic fine powdered silica is hydrophobized at the stage of preparing the adhesive of the present invention.

[0089] Specific examples of silica fillers include hydrophilic finely powdered silica such as Aerosil (registered trademark) 50, 130, 200 and 300 (trade names, manufactured by Nippon Aerosil Co., Ltd.), Cabosil (registered trademark) MS-5 and MS-7 (trade names, manufactured by Cabot Corporation), Reolosil QS-102 and 103 (trade names, manufactured by Tokuyama Corporation), and Nipsil LP (trade name, manufactured by Nippon Silica Co., Ltd.); and hydrophobic finely powdered silica such as Aerosil (registered trademark) R-812, R-812S, R-972 and R-974 (trade names, manufactured by Degussa Co., Ltd.), Reolosil MT-10 (trade name, manufactured by Tokuyama Corporation), and Nipsil SS series (trade names, manufactured by Nippon Silica Co., Ltd.).

[0090] When fine silica powder is used, the blending amount is usually 1 to 50 mass% calculated as solid content. If the blending amount is less than 1 mass%, the strength imparting effect of the silica filler is likely to be insufficient, and if it exceeds 50 mass%, the obtained silicone resin composition is likely to be significantly lacking in fluidity and to be inferior in workability.

[0091] As the adhesion promoter, for example, an organic titanium compound, such as an organic acid salt of titanium, can be used. The adhesion promoter can be used as a catalyst to further accelerate the curing of the silicone resin composition and further improve its adhesiveness. The adhesion promoter can be used alone or in combination of two or more kinds.

[0092] Examples of the adhesion promoter include titanium chelate compounds, alkoxy titanium, and combinations thereof. Specific examples of titanium chelate compounds include diisopropoxy bis(acetylacetonato) titanium, diisopropoxy bis(ethylacetoacetato) titanium, dibutoxy bis(methylacetoacetato) titanium, and the like. Specific examples of alkoxy titanium include tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, and the like. The alkoxy group in the alkoxy titanium may be linear or branched.

[0093] The amount of the adhesion promoter is preferably 0.01 to 10 mass %, more preferably 0.1 to 5 mass %, calculated as solid content. If the amount is less than the lower limit of the above range, the adhesiveness improving effect may not be easily achieved, whereas if the amount is more than the upper limit of the above range, the surface curing of the resulting adhesive may become too rapid. There may be cases where it is too long.

[0094] Silane coupling agents are compounds that have an alkoxy group bonded to a silicon atom and a reactive group that chemically bonds with an adherend such as a metal or various synthetic resins in one molecule, and compounds that have an alkenyl group or a hydrogen atom may be used instead of the alkoxy group bonded to the silicon atom. Epoxy groups or acrylic groups may be used as the reactive group that chemically bonds with the adherend.

[0095] When applying a silicone resin, a primer may be applied to the material to be applied before application. As the primer, a silicone resin of a condensation curing type, an addition curing type, or the like can be used. The amount of primer applied is 0.1 to 1.2 g / m 2 is preferred.

[0096] Examples of silicone resins include "SYLGRAD186", "DOWSIL3-6512", "SYLGRAD527", "DOWSILX3-6211", "SYLGRAD3-6636", "DOWSIL SE1880", "DOWSIL SE960", "DOWSIL781 Acetoxy Silicone", "DOW CORNING SE9187", "DOWSIL Q1-4010", "SYLGRAD 1-4128", "DOWSIL 3140 RTV Coating", "DOWSIL HC2100", "SIL-OFF Q2-7785", "Silaseal 3FW", "Silaseal DC738RTV", "DC3145", and "DC3140" (all manufactured by Dow Corning Corporation), "ELASTOSIL RT707W", "ELASTOSIL EL4300", "ELASTOSIL M4400", "ELASTOSIL M8012", and "SILRES BS CREME C”, “SILRES BS 1001”, “SILRES BS 290”, “ELASTSIL 912”, “ELASTSIL E43N”, “ELASTOSIL N9111”, “ELASTOSIL N199”, “SEMICOSIL 987GR”, “ELASTOSIL RT772”, “ELASTOSIL RT745”, “ELASTOSIL LR3003 / 05", "ELASTOSIL LR3343 / 40", "ELASTOSIL LR3370 / 40", "ELASTOSIL LR3374 / 50BR", "ELASTOSIL EL1301", "ELASTOSIL EL 4406", "ELASTOSIL EL3530", "ELASTOSIL EL 7152”, “ELASTOSIL R401 / 10OH”, “SILPUREN21XX series" (manufactured by Asahi Kasei Wacker Silicone Co., Ltd.), "KE-3423", "KE-347", "KE-3479", "KE-1830", "KE-1820", "KE-1056", "KE-1800T", "KE-66", "KE-1031", "KE-12", "KE-1300T", "SD4584PSA", "KS-847T", "KF-2005", "KNS-3002", "KR-100", "KR-101-10", "KR-130", "KR-3600", "KR-3704", "KR-3700", "KR- 3701", "X-40-3237", "X-40-3291-1", "X-40-3240", "Sealant 45", "Sealant Master 300", "Sealant 72", "KE-42", "Sealant 70", "KE-931-U", "KE-9511-U", "KE-541-U", "KE-153-U", "KE-361-U", "KE-1950-10", "KEG-2000-40", "KE-2019-40", "KE-2090-50", "KE-2096-60" (manufactured by Shin-Etsu Chemical Co., Ltd.) and the like can be used. A catalyst may be further added to the silicone-based resin. As the catalyst, organic acid salts such as zinc octylate, iron octylate, cobalt, and tin, and amine-based catalysts can be used. In addition, organic tin compounds, organic titanium compounds, and platinum compounds can also be used. As the catalyst, for example, "CAT-PL-50T" (manufactured by Shin-Etsu Chemical Co., Ltd.) or "NC-25" (manufactured by Toray Dow Corning Co., Ltd.) can be used. In addition, when applying, a solvent such as toluene, xylene, or alcohols may be added. As the primer, "Primer AQ-1", "Primer C", "Primer MT", and "Primer T" can be used. "Primer D", "Primer A-10", "Primer R-3", "Primer A-20" (manufactured by Shin-Etsu Chemical Co., Ltd.), etc. can be used.

[0097] The method of forming the gas-permeable non-porous layer is not particularly limited, and the gas-permeable non-porous layer can be produced by laminating the gas-permeable non-porous layer on the porous substrate using a reverse roll coater, a positive rotation roll coater, a gravure coater, a knife coater, a rod coater, a slot orifice coater, an air doctor coater, a kiss coater, a blade coater, a cast coater, a spray coater, a spin coater, an extrusion coater, a hot melt coater, or the like. The gas-permeable non-porous layer can also be produced by a method such as powder coating or electrodeposition coating. The substrate may be coated by immersing it in the raw material liquid of the gas-permeable non-porous layer. The substrate may be in the form of a sheet or a hollow fiber. In a step before the coating, a pretreatment such as primer coating or corona treatment may be performed.

[0098] The mass of the gas-permeable non-porous layer 212 is 10 g / m 2 More than 500g / m 2 It is preferable that the following is true: , 20g / m 2 More than 200g / m 2 It is more preferable that the weight per unit area of ​​the gas-permeable non-porous layer 212 is equal to or less than the above. is the basis weight E (g / m 2 ) of the substrate before the gas-permeable non-porous layer 212 is laminated. 2 ) and non-gas permeable The basis weight F (g / m) of the gas-permeable non-porous layer 212 and the substrate after the porous layer is laminated 2 ) and D (g / m2) can be calculated using the following formula (1).

[0099] [Formula 1] D=FE

[0100] The weight of the gas-permeable non-porous layer 212 and the base material is JIS1913:2010 General nonwoven fabric test method 6.2 unit area It is measured in mass per volume.

[0101] The thickness of the gas-permeable non-porous layer 212 is preferably 10 um or more and 500 um or less, and more preferably 20 um or less. The thickness of the gas-permeable non-porous layer 212 is a value measured according to JIS 1913:2010 General Nonwoven Fabric Testing Method 6.1 Thickness Measurement Method.

[0102] (Microbial support layer 213) The microorganism support layer 213 is a layer that holds microorganisms on its surface or inside, has a space inside where microorganisms can grow, and allows organic matter in water to pass through. Examples of materials for the microorganism support layer 213 include porous sheets such as mesh, woven fabric, nonwoven fabric, foam, or microporous membrane. Examples of materials for the porous sheet include polyolefin resin, polystyrene resin, polyester resin, polyvinyl chloride resin, acrylic resin, urethane resin, epoxy resin, polyamide resin, methyl cellulose resin, ethyl cellulose resin, polyvinyl alcohol resin, vinyl acetate resin, phenol resin, fluororesin and polyvinyl butyral resin, polyimide, polyphenylene sulfide, para- and meta-aramid, polyarylate, carbon fiber, glass fiber, aluminum fiber, steel fiber, ceramic, etc. Considering microbial adhesion and processability, polyolefin resin, polyester resin, polyamide resin, acrylic resin, polyurethane resin, and carbon fiber are preferred.

[0103] The weight of the microbial support layer 213 is 2 g / m 2 More than 500g / m 2 It is preferable that the weight is less than 10 g / m 2 More than 200g / m 2 The basis weight of the microorganism support layer 213 is a value measured by mass per unit area according to JIS1913:2010 General Nonwoven Fabric Testing Method 6.2. The basis weight of the microorganism support layer 213 is 2 g / m 2 By setting the thickness to the above value, it is possible to obtain an effect that the surface becomes uneven, which makes it easier for microorganisms to be retained on the microorganism support layer 213. In addition, the basis weight of the microorganism support layer 213 is set to 500 g / m 2By satisfying the following, it is possible to obtain the effect that spaces in which microorganisms can grow are generated inside the microorganism support layer 213, making it easier to retain the microorganisms, and that the spaces make it easier to supply oxygen to the microorganisms.

[0104] The thickness of the microorganism support layer 213 is preferably 5 um or more and 2000 um or less, and more preferably 20 um or more and 500 um or less. The thickness of the microorganism support layer 213 is a value measured according to JIS1913:2010 General Nonwoven Fabric Testing Method 6.1 Thickness Measurement Method.

[0105] The microbial support layer 213 may be formed by surface treatment of the substrate 211. In this way, the surface treatment can increase the surface roughness and membrane potential of the substrate 211, improving the adhesion of microorganisms. For example, the surface treatment may involve graft polymerization of glycidyl methacrylate and further reaction with diethylamine or sodium sulfite. Alternatively, the surface treatment may involve graft polymerization of glycidyl methacrylate and then reaction with ammonia or ethylamine.

[0106] (Method of manufacturing gas supplier 10) The manufacturing method of the gas supplier 10 of this embodiment is carried out according to the flow chart shown in Fig. 7. Hereinafter, the manufacturing method of the gas supplier 10 will be described with reference to Fig. 7.

[0107] First, in step S11 of FIG. 7, a member such as cardboard constituting the gas-sending layer 12 is placed in a predetermined position (placement step).

[0108] Next, in step S12 of FIG. 7, a plurality of through holes as gas passage holes 13 are formed in the front liner 12b and the back liner 12c of the gas-transporting layer 12 using a needle material (hole forming step).

[0109] The needle material may be, for example, a roll (needle material) with multiple needles attached to its surface, or a needle material with one needle attached that allows the gas passing holes 13 to be formed manually. By using these needle materials, the necessary gas passing holes can be easily formed even when the gas-delivery layer is covered with a plate material or the like. When the roll is used, the gas-delivery layer 12 is passed between the roll and a flat surface to form the gas passing holes 13 in the gas-delivery layer 12. The flat surface may be, for example, the surface of a flat plate or the surface of another roll to which no needles are attached.

[0110] The gas passage holes 13 may be formed by pressing a plate with needles arranged on its surface against the surface of the gas delivery layer 12, or may be formed using a blade such as a cutter knife.

[0111] Next, in step S13 of Figure 7, two approximately rectangular sheet laminates 21, 21 are stacked together and the peripheral edges of the base materials 211, 211 of the sheet laminates 21, 21 are joined by thermal fusion to form a bag made of the sheet laminates 21, 21 (see Figure 4 for the base materials 211).

[0112] Specifically, as shown in Fig. 8, in a state where sheet laminates 21, 21 unwound from two rolls R1, R2 are overlapped, three peripheral sides of base materials 211, 211 of the sheet laminates 21, 21 are joined together by thermal welding to form a thermally welded portion 21c. Then, in a state where the three sides are sealed by the thermally welded portion 21c, the sheet laminates 21, 21 are cut at a portion that will become the opening 21b (Fig. 8(a) is a perspective view of the sheet laminates 21, 21, and Fig. 8(b) is a cross-sectional view of the sheet laminates 21, 21).

[0113] The method of forming a bag from the sheet laminate 21 is not limited to the above. For example, a bag may be formed by gluing only one opening of the sheet laminate 21 formed into a cylindrical shape. Alternatively, a single sheet laminate 21 may be folded in half and the left and right ends may be heat-sealed to form a bag. Alternatively, the sheet laminate may be formed into a bag shape by inflation molding or the like. Alternatively, a bag made of the gas-permeable nonporous layer 21 may be formed. Alternatively, the hollow fiber-shaped sheet laminate 21 may be obtained by continuous molding. For example, the sheet laminate 21 may be obtained by continuously immersing a substrate in the raw material liquid of the gas-permeable nonporous layer 212 and fixing it by heat treatment, cooling, or the like as necessary, or the sheet laminate 21 may be obtained by continuously disposing the raw material liquid of the gas-permeable nonporous layer 212 on a hollow substrate using a mold and fixing it by heat treatment, cooling, or the like as necessary.

[0114] The temperature for heat fusion is preferably equal to or higher than the melting point and equal to or lower than the thermal decomposition temperature of the base material 211 made of a thermoplastic resin.

[0115] The method for bonding the sheet laminate 21 is not limited to the above-mentioned heat fusion, and the sheet laminate 21 may be bonded using, for example, double-sided tape, adhesive, etc. The adhesive material is preferably one having at least one of water resistance, waterproofing, chemical resistance, and microbial decomposition resistance.

[0116] Next, in step S14 of FIG. 7, as shown in FIG. 9, the gas-sending layer 12 having the gas passage holes 13 formed therein is inserted into the bag interior 21d from the opening 21b of the bag made of the sheet laminate 21 (covering step).

[0117] The gas-sending layer 12 is inserted from the opening 21b in the direction of the gas flow path S formed by the core material 12a and the like.

[0118] According to the wastewater treatment device 50 of this embodiment, gas from the gas supply source 53 is supplied to the upper end 21b of the gas-sending layer 12. The gas supplied to the upper end 21b flows through the gas flow path S and passes through the gas passing hole 13, and the gas passing through the gas passing hole 13 is supplied into the wastewater W via the sheet laminate 21. As a result, oxygen is supplied to the microorganisms in the wastewater W, activating the microorganisms, and the organic matter or nitrogen source in the wastewater W can be efficiently decomposed by the activity of the microorganisms to purify the wastewater.

[0119] According to the sheet laminate 21 of the present embodiment, since the substrate 211, which is a microporous film, and the gas-permeable non-porous layer 212 are included, the purification performance of the wastewater treatment device 50 can be maintained.

[0120] That is, since the substrate 211 is a microporous membrane with high smoothness, the substrate 211 can be covered with the gas-permeable nonporous layer 212 without causing defects in the gas-permeable nonporous layer 212. As a result, waterproofness can be obtained even if the gas-permeable nonporous layer 212 covering the substrate 211 is thin. Therefore, the waterproofness of the sheet laminate 21 can be improved without impairing the gas permeability of the sheet laminate 21. Furthermore, by covering the substrate 211 with the gas-permeable nonporous layer 212, the pores of the substrate 211 (microporous membrane) can be prevented from becoming hydrophilic. Therefore, the sheet laminate 21 can maintain waterproofness for a long period of time. From the above, if the sheet laminate 21 of this embodiment covers the gas-transporting layer 12, gas can be supplied from the gas-transporting layer 12 side through the sheet laminate 21 into the wastewater W without permeating liquid to the gas-transporting layer 12 side. Therefore, the purification performance of the wastewater treatment device 50 is maintained. Furthermore, according to this embodiment, by inserting the gas-transporting layer 12 into the bag formed from the sheet laminate 21, it is possible to easily achieve a state in which the gas-transporting layer 12 is covered with the sheet laminate 21.

[0121] Furthermore, according to the sheet laminate 21 of the present embodiment, the microorganism support layer 213 is included, so that the purification performance of the wastewater treatment device 50 can be improved.

[0122] That is, by including the microorganism support layer 213 in the sheet laminate 21, the microorganisms adhere to the microorganism support layer 213. Therefore, a sufficient amount of gas can be continuously supplied to the microorganisms, so that the microorganisms are reliably and continuously activated. This improves the purification performance of the wastewater treatment device 50. It is possible.

[0123] Furthermore, according to this embodiment, the sheet laminate 21 is laminated in the order of the microorganism support layer 213, the base material 211, and the gas-permeable non-porous layer 212, so that the outermost layer of the sheet laminate 21 that contacts the wastewater W can be constituted by the microorganism support layer 213. Therefore, the microorganisms can be reliably attached to the microorganism support layer 213, and the microorganisms can be reliably activated. Therefore, the purification performance of the wastewater treatment device 50 can be reliably improved. In particular, when the microorganisms contained in the wastewater W are aerobic microorganisms, the aerobic microorganisms gather on the sheet laminate 21 by supplying gas into the wastewater W through the sheet laminate 21. Therefore, many microorganisms adhere to the microorganism support layer 213, and the purification performance of the wastewater treatment device 50 is significantly improved.

[0124] The sheet laminate 21 has an oxygen supply rate Q (gO2 / m) obtained by the method shown in the following (oxygen supply test). 2 / day) is 25g / m 2 / day or more, and 26 g / m 2 / day or more is more preferable, and 27 g / m 2 The upper limit of the oxygen supply rate Q is, for example, 60 g / m 2 It is preferable to use / day.

[0125] (Oxygen supply performance test) Ion-exchanged water is poured into a sealed tank having a cubic shape with one side being 7 cm long and one vertical side being made of a membrane, and the oxygen concentration inside the sealed tank is continuously measured while stirring the ion-exchanged water by rotating the rotor of a stirrer in an environment of 23 to 27°C. The ion-exchanged water is added with sodium sulfite at a concentration of 100 mg / L and cobalt chloride at a concentration of 1.5 mg / L or more. The stirrer used is the "HE-20GB" manufactured by Koike Precision Machinery Manufacturing Co., Ltd., and the rotation speed is set to HIGH range. The scale is set to 7. The oxygen supply performance is evaluated in an environment of 23℃ to 27℃, and an approximate line is calculated from the correlation between the time series data of the measured oxygen concentration and the common logarithm of the oxygen deficiency against time t (h) (Y=log10(Cs-C)), and the slope Z of the approximate line against time t is calculated. Cs is where T is the saturated oxygen concentration in the liquid phase at the measurement temperature, and C is the measured oxygen concentration in the liquid phase at the measurement time t. From the slope Z, the oxygen supply rate Q(gO 2 / m 2 / day) is calculated according to the following formula (2).

[0126] [Formula 2] TIFF0007612762000001.tif17146

[0127] Other embodiments of the present invention will be described below. In the following embodiments, configurations for which materials are not specifically specified may be made of the same materials as in the first embodiment. The gas supplier shown in the following embodiments can also be unitized, and a supplier unit in which the gas supplier is unitized can be disposed in a wastewater treatment device.

[0128] (Embodiment 2) The gas supplier 110 according to the second embodiment of the present invention will be described below with reference to FIGS.

[0129] The gas supply unit 110 of this embodiment differs from the gas supply unit 10 of the above-mentioned first embodiment (FIG. 4) in that a porous sheet 131 is disposed between the gas-delivery layer 12 and the sheet laminate 21.

[0130] The porous sheet 131 may be, for example, a mesh sheet, a woven fabric, a nonwoven fabric, or a microporous membrane. There can be.

[0131] In addition, examples of materials for the porous sheet 131 include polyolefin resin, polystyrene resin, polyester resin, polyvinyl chloride resin, acrylic resin, urethane resin, epoxy resin, polyamide resin, methyl cellulose resin, ethyl cellulose resin, polyvinyl alcohol resin, vinyl acetate resin, phenol resin, fluororesin, and polyvinyl butyral resin.

[0132] From the viewpoint of gas permeability, it is particularly preferable that the porous sheet 131 is made of paper, polyolefin resin, polystyrene resin, PVC resin, or polyester resin.

[0133] When the porous sheet 131 is laminated, the adhesive may be applied only to the outer periphery, or, if gas can be supplied to the sheet laminate 21, the entire surface of the porous sheet 131 may be adhered to the sheet laminate 21 and the gas-delivery layer 12.

[0134] As a result, by interposing the porous sheet 131 between the sheet laminate 21 and the gas-delivery layer 12, as shown in Fig. 11, the gas can move within the porous sheet 131 in the surface direction of the gas-delivery layer 12. Therefore, compared to a configuration without the porous sheet 131, the gas delivered from the gas passing holes 13 of the gas-delivery layer 12 can be supplied to the sheet laminate 21 over a wider range in the surface direction of the gas-delivery layer 12 (the plane direction of the liners 12b, 12c).

[0135] As a result, gas is not supplied locally from the sheet laminate 21 in contact with the wastewater W, but can be supplied into the wastewater W from a wider area, compared to a configuration in which the porous sheet 131 is not interposed.

[0136] Furthermore, by positioning the porous sheet 131 so as to be sandwiched between the gas-delivery layer 12 and the sheet laminate 21, the gas-delivery layer 12 is in close contact with the sheet laminate 21, thereby preventing the movement of gas from being blocked.

[0137] Furthermore, since the nonwoven fabric constituting the porous sheet 131 has many fine air holes, it is expected to have the effect of preventing the porous sheet 131 from becoming airtight.

[0138] For example, the unevenness may be formed on the surface of the sheet laminate 21 opposite to the surface in contact with the wastewater W. Even with this configuration, the same effect as when a porous sheet is disposed can be achieved.

[0139] (Items that can be changed in the first and second embodiments) In the above-mentioned first and second embodiments, an example in which a flat gas supply body 10 is used has been described. However, the present invention is not limited to this. For example, the gas supply body 10 may be wound, or a gas supply body molded into a cylindrical shape may be used.

[0140] In the above first and second embodiments, the gas supply body 10 is constructed by inserting the gas-delivery layer 12 through the opening 21b of the bag made of the sheet laminate 21. However, the present invention is not limited to this. For example, the sheet laminate may be laminated and bonded to the surface of the gas-delivery layer. The bonded portion may be only the outer periphery of the sheet laminate, or the sheet laminate and the gas-delivery layer may be bonded over the entire surface as long as gas can be supplied to the sheet laminate.

[0141] The members constituting the gas-sending layer are not limited to the hollow plate-like members shown in the above-mentioned embodiments 1 and 2, and may be changed as shown in Fig. 12. The gas-sending layer 311 shown in Fig. 12 is formed by combining a first structure 312 having a honeycomb structure with a second structure 313 having a honeycomb structure in which cells (gas passing holes 313a) different in size from the cells (gas passing holes 312a) of the first structure 312 are arranged.

[0142] In the above-mentioned first and second embodiments, an example was described in which the gas-transmitting layer 12 includes a core 12a, a front liner 12b, and a back liner 12c. However, the present invention is not limited to this. For example, as shown in Fig. 13, a hollow plate-shaped member 412 having a corrugated core 412a in a cross-sectional view arranged along the gas flow path S and arranged between a front liner 412b and a back liner 412c having a plurality of gas passage holes 413 may be used as the gas-transmitting layer.

[0143] The inventors of the present application have produced sheet laminates according to the embodiments of the present invention and sheet laminates according to the comparative examples, and conducted tests to confirm the leak pressure, oxygen supply performance, treatment performance, and long-term leak performance of these embodiments and comparative examples, and the results are shown in Table 1. The tests will be described below.

[0144] [Table 1] TIFF0007612762000003.tif127170

[0145] Example 1 In Example 1, the microorganism support layer 213, the substrate 211, and the gas-permeable non-porous layer 212 were laminated in this order. A microporous membrane included in Celpore NW07H manufactured by Sekisui Chemical Co., Ltd. was used as the substrate 211, and a polyolefin nonwoven fabric included in the above Celpore NW07H was used as the microorganism support layer 213 (Celpore NW07H has a three-layer structure of nonwoven fabric, microporous membrane, and nonwoven fabric, of which one of the nonwoven fabrics was used as the microorganism support layer 213, and the polyolefin microporous membrane was used as the substrate 211). The thickness of the substrate 211 was 90 um. The basis weight of the microorganism support layer 213 was 10 g / m 2 , and the thickness was 25um.

[0146] In Example 1, a mixture of a methylvinyl silicone resin, a crosslinking agent, a platinum catalyst, and the like is applied onto the substrate 211 using a bar coater, and then the substrate is left in an atmosphere of 70° C. for 1 hour. By leaving it still, the gas-permeable non-porous layer 212 is laminated on the substrate 211. The silicone resin used is Wacker Asahi Kasei Silicone Co., Ltd., product number "NC1910", and the silicone resin has a basis weight of 20 g / m after curing. 2 It is.

[0147] Example 2 In Example 2, a urethane resin, model number "Heimuren Y-237NS" manufactured by Dainichi Seika Chemicals Co., Ltd., was used instead of a silicone resin to form the gas-permeable non-porous layer 212, and the characteristics of the resin Coating weight: 10g / m 2 The rest is the same as in Example 1.

[0148] Example 3 In Example 3, the weight of the resin constituting the gas-permeable non-porous layer 212 is 40 g / m 2 Other than that is the same as in Example 1.

[0149] Example 4 In Example 4, the weight of the resin constituting the gas-permeable non-porous layer 212 is 80 g / m 2 Other than that, the present embodiment is the same as the first embodiment.

[0150] Example 5 Example 5 is similar to Example 3, except that a microporous film (thickness: 40 μm) manufactured by 3M was used as the substrate 211 .

[0151] Example 6 Example 6 is similar to Example 4, except that Mitsubishi Plastics' Exepole E BSPBX-4 (film thickness 23 μm) was used as the base material 211 .

[0152] Example 7 Example 7 is the same as Example 3, except that the microbial support layer 213 used was ELBES SO203WDO (basis weight 20 g / m 2 ) manufactured by Unitika Ltd.

[0153] Example 8 Example 8 is the same as Example 3, except that the microorganism support layer 213 used was ELBES T0503WDO (basis weight 50 g / m 2 ) manufactured by Unitika Ltd.

[0154] Example 9 In Example 9, the weight of the resin constituting the gas-permeable non-porous layer 212 was 100 g / m 2 Other than that is the same as in Example 1.

[0155] Example 10 In Example 10, the microbial support layer 213 was made of Elves T0703WDO (weight 70 g / m) manufactured by Unitika Ltd. 2 The procedure was the same as in Example 5, except that a 1-methyl-2-propanediol was used.

[0156] Example 11 In Example 11, the weight of the resin constituting the gas-permeable non-porous layer 212 is 8 g / m 2 Other than that, the present embodiment is the same as the first embodiment.

[0157] Example 12 Example 12 was the same as Example 1, except that the gas-permeable non-porous layer 212 was continuously produced using a reverse roll coater and a heating device associated therewith.

[0158] (Example 13) Example 13 is similar to Example 5, except that the gas-permeable non-porous layer 212 is continuously produced using a slit coater and a heating device associated therewith.

[0159] Example 14 Example 14 is similar to Example 1, except that an ultraviolet-curable silicone resin mixture is applied onto a substrate 211 using a reverse roll coater, and then cured by irradiation with ultraviolet rays.

[0160] Example 15 In Example 15, the substrate 211 is a moisture permeable film manufactured by Sekisui Film Co., Ltd., a microporous film of Celpore NW07H. Using only the porous membrane, a resin layer was laminated on the microporous membrane in the same manner as in Example 2. A polyolefin nonwoven fabric contained in the above-mentioned Celpore NW07H was laminated on top of the fat layer and left to stand for 1 hour in an atmosphere of 70° C. to obtain a sheet laminate of Example 10 having a substrate 211, a gas-permeable resin layer, and a microbial support layer 213 in that order.

[0161] Example 16 Example 16 is similar to Example 1, except that the microbial support layer 213 was not used.

[0162] Comparative Example 1 Comparative Example 1 is similar to Example 1, except that no gas-permeable non-porous layer is used.

[0163] Comparative Example 2 In Comparative Example 2, a polyester nonwoven fabric (model number "Marix 82607WSO" manufactured by Unitika Ltd.) was used as the base material 211, and a resin layer was laminated on the nonwoven fabric in the same manner as in Example 1. The resin weight of the body-permeable non-porous layer is 20g / m 2 It was.

[0164] (Leak pressure) The tests to check the leak pressure are mainly based on JIS K 6404-7:1999, A21: High water pressure -Leak pressure was measured using a method that was partially modified from the small sample method (dynamic pressure method). The leak pressure is the pressure gauge value when water first appears through the test piece. The differences from the high water pressure small sample method (dynamic pressure method) are listed below.

[0165] A support nonwoven fabric (Unitika Marix 82607WSO) was placed on the opposite side of the sheet laminate to the side to which water pressure was applied. The water used in the test was ion-exchanged water with added food coloring. The water pressure was increased at a rate of 0.1 MPa per minute.

[0166] (Oxygen supply performance) In the test to confirm the oxygen supply performance, the oxygen supply rate Q (gO2 / (m 2 ·d)) was sought.

[0167] (Purification treatment performance) In the purification treatment performance test, a sealed tank having a cube shape with sides of 7 cm and one vertical side formed of a laminated sheet is placed in a thermostatic chamber at a temperature of 30±2°C with organic matter-containing water having the following characteristics (1), (2), and (3) inside the sealed tank. (1) Soluble starch 0.8g / L, peptone 0.084g / L, yeast extract 0.4g / L, urea 0.052g / L, CaCl2 0.055g / L, KH2PO4 0.017g / L, MgSO4·7H2O 0.001g / L, KCl 0.07g / L , NaHCO3 was added at a concentration of 0.029 g / L. (2) The solvent is tap water. (3) 5g of soil microorganisms were added to decompose organic matter.

[0168] The organic matter-containing water in the sealed tank is replaced every time the organic matter-containing water is continuously stirred by rotating a stirrer for 3.5 days, and this operation is continued for 28 days and 56 days (i.e., the operation of "stirring the organic matter-containing water for 3.5 days → discharging the organic matter-containing water in the sealed tank → putting the organic matter-containing water into the sealed tank" is repeated for 28 days and 56 days). After this, the sealed tank is filled with the organic matter-containing water and the CODCr concentration is measured. Then, using the CODCr concentration A mg / L at the time when the sealed tank is filled with the organic matter-containing water (after 28 days and 56 days) and the CODCr concentration B mg / L three days after the time when the sealed tank is filled with the organic matter-containing water (after 31 days and 59 days), the following CODCr concentration is calculated. The organic matter removal rate R can be calculated from equation (3).

[0169] [Formula 3] R = (1-B / A) × 100 (3)

[0170] (Long-term leak performance) The long-term leak performance was evaluated by visually observing the air side surface of the sheet laminate placed in the wastewater treatment device or by checking for the presence or absence of leakage using cobalt chloride paper.

[0171] In Comparative Example 1, which did not have a gas-permeable non-porous layer, the leak pressure was 0.16 MPa. When a wastewater treatment device was constructed using Comparative Example 1 and its performance was evaluated, water leakage to the air side of the sheet was observed after two months, and the long-term leak performance was poor. In addition, the purification treatment performance of Comparative Example 1 could not be measured due to the water leakage.

[0172] In Comparative Example 2, in which the substrate was made of a PET / PE nonwoven fabric, the leak pressure was 0.05 MPa. In the wastewater treatment device using Comparative Example 2, water leakage to the air side of the sheet was observed after two months, and the long-term leakage performance was poor. Also, due to the water leakage, the purification treatment performance of Comparative Example 2 could not be measured.

[0173] In contrast, in Examples 1 to 16 in which the substrate was made of a microporous membrane, the leak pressure was 0.2 MPa or more, which was higher than those in Comparative Examples 1 and 2. Furthermore, in the wastewater treatment device using Examples 1 to 16, no water leakage to the air side of the sheet was observed over a long period of time, and the long-term leak performance was good. From the above, it was confirmed that the waterproofing can be improved by providing the substrate made of a microporous membrane in the sheet laminate.

[0174] Furthermore, when Examples 1, 3 to 14, and 16 in which the resin of the gas-permeable non-porous layer is silicone are compared with Examples 2 and 15 in which the resin of the gas-permeable non-porous layer is urethane, the oxygen supply performance of each of Examples 1, 3 to 14, and 16 was higher than the oxygen supply performance of Examples 2 and 15. This confirmed that the oxygen supply performance of the sheet laminate could be improved by using silicone as the resin of the gas-permeable non-porous layer.

[0175] In addition, when Examples 1 to 15 having a microbial support layer were compared with Example 16 not having a microbial support layer, the organic matter removal rates of Examples 1 to 15 were all higher than the organic matter removal rate of Example 16. This confirmed that the provision of a microbial support layer on the sheet laminate can improve the purification performance of the wastewater treatment device.

[0176] (Embodiment 3) Next, a third embodiment of the present invention will be described below. Fig. 14 is a vertical cross-sectional view showing a gas supplier 80 according to the third embodiment.

[0177] The gas supplier 80 according to the third embodiment includes the gas-delivery layer 12 shown in Fig. 5 and a sheet laminate 81, and the gas-delivery layer 12 is disposed in a bag formed by the sheet laminate 81. Note that the gas-delivery layer 12 may be replaced by a gas-delivery layer 311 shown in Fig. 12 or a hollow plate-like member 412 shown in Fig. 13.

[0178] In the sheet laminate 81 of the third embodiment, the gas-permeable non-porous layer 212 has adhesiveness, and the microorganism support layer 213, the gas-permeable non-porous layer 212, and the substrate 211 are laminated in this order from the side in contact with the wastewater, and the surface of the adhesive gas-permeable non-porous layer 212 that contacts the wastewater serves as the microorganism support layer 213. Alternatively, the sheet laminate 81 has the microorganism support layer 213, the substrate 211, and the gas-permeable non-porous layer 212 laminated in this order from the side in contact with the wastewater, similar to the sheet laminate 21 shown in FIG. In this case, the gas-permeable non-porous layer 212 is also adhesive.

[0179] The gas-permeable non-porous layer 212 has adhesiveness, which makes it easy for the biofilm 214 to settle, and has gas permeability, which makes it possible to efficiently supply gases such as oxygen required by the microorganisms that make up the biofilm 214 to the biofilm 214. The biofilm 214 is a microbial film made up of a plurality of microorganisms, and is composed of aerobic microorganisms and their products.

[0180] The sheet laminate 81 of the third embodiment has gas permeability and is also capable of supporting microorganisms, so that the distance from the gas-sending layer 12 to the outermost layer can be shortened. As a result, it becomes possible to sufficiently supply oxygen to the biofilm 214, and the biofilm 214 becomes less likely to peel off.

[0181] The gas-permeable non-porous layer 212 having adhesiveness means that the gas-permeable non-porous layer 212 feels sticky when touched with a finger. More specifically, in an inclined ball tack test method of a sheet test method using JIS Z0237-14 adhesive tape, the ball number at an inclination angle of 30 degrees is preferably 1 or more, and more preferably 2 or more. There is no particular limit to the upper limit of the ball number obtained by the inclined ball tack test method, and for example, it is preferably 32 or less, and more preferably 10 or less. When the gas-permeable non-porous layer 212 has adhesiveness within this range, the biofilm 214 is less likely to peel off, and the wastewater treatment performance is improved or stabilized.

[0182] An example of the gas-permeable non-porous layer 212 is formed by applying a resin composition for forming a film (for forming a film for water treatment). As the application means, a wide variety of known application methods can be adopted, and there is no particular limitation. For example, a reverse roll coater, a positive rotation roll coater, a gravure coater, a knife coater, a rod coater, a slot orifice coater, an air doctor coater, a kiss coater, a blade coater, a cast coater, a spray coater, a spin coater, an extrusion coater, a hot melt coater, a bar coater, and a die coater can be exemplified. In addition, the gas-permeable non-porous layer 212 may be obtained by coating the substrate 211 as shown below by immersing it in a resin composition for forming a film. In a step before the application, a pretreatment such as primer application or corona treatment may be performed. Furthermore, the gas-permeable non-porous layer 212 may be made only from the film-forming resin composition by extrusion molding, inflation molding, calendar molding, or the like, and in this case, the sheet laminate 81 may be obtained by multi-layer molding with the substrate 211 as described below. Stretching may be performed after the above molding.

[0183] As the resin contained in the resin composition for forming a membrane (for forming a membrane for water treatment), a wide variety of known adhesive resins can be adopted, and there is no particular limitation. Among them, in order to improve the adhesiveness of the gas-permeable non-porous layer 212, it is preferable to use a resin that functions as an adhesive. Specifically, as such a resin, in addition to a resin that is a rubber-like substance and an acrylic-based resin that contains an acrylic monomer as an essential component, it is also preferable to use a urethane-based resin, a polycarbonate-based resin, a polyester-based resin, a polyolefin-based resin, an acrylic urethane-based resin, a vinyl-based resin, a silicone-based resin, or a resin composition of adhesive grade thereof. Specific examples of the rubber-like substance include polybutadiene rubber, styrene-butadiene copolymer rubber, ethylene-propylene rubber, butadiene-acrylonitrile copolymer rubber, butyl rubber, acrylic rubber, styrene-isobutylene-butadiene copolymer rubber, and isoprene-acrylic acid ester copolymer rubber. In addition, as the polyolefin-based resin, more specifically, a resin with high oxygen permeability such as polymethylpentene may be used. These resins may be used alone or in combination as copolymers of two or more kinds. In addition, a solvent such as toluene or xylene may be mixed during coating.

[0184] In order to increase the adhesion of the resin composition for film formation, a resin having adhesion may be added. The amount of the adhesive resin is preferably 5 to 70% by mass, more preferably 10 to 65% by mass, in 100% by mass of the resin composition for film formation in order to improve the compatibility with the catalyst and the solvent and to facilitate viscosity adjustment.

[0185] It is also preferable to add a polymerization initiator to the film-forming resin composition in order to impart the film-forming resin composition with the property of being cured by thermal energy or light energy.

[0186] When the curing is performed by thermal energy, it is preferable to use an organic peroxide-based or diazonium-based polymerization initiator as the thermal polymerization initiator. In this case, the content of the polymerization initiator is preferably 0.1 to 5.0% by mass in 100% by mass of the film-forming resin composition.

[0187] When curing is performed by light energy such as ultraviolet light or visible light, known photopolymerization initiators can be widely used as the polymerization initiator. Specifically, benzoin, isopropyl benzoin ether, isobutyl benzoin ether, benzophenone, Michler's ketone, chlorothioxanthone, dodecyl thioxanthone, dimethyl thioxanthone, diethyl thioxanthone, acetophenone diethyl ketal, benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, etc. are mentioned, among which benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, etc. are preferably used. In addition, as the cationic photopolymerization initiator, initiators such as onium salt, tri(substituted)phenylsulfonium, diazosulfone, and iodonium are preferably used. In addition, as the anionic photopolymerization initiator, organometallic initiators such as alkyl lithium can be preferably used. These may be used alone or in combination of two or more kinds.

[0188] When a photopolymerization initiator is used, the amount of the photopolymerization initiator contained in 100% by mass of the film-forming resin composition is preferably 0.1 to 10.0% by mass. If the amount of the photopolymerization initiator used is below the lower limit, the adverse effect of poor curing is likely to occur. On the other hand, if the amount exceeds the upper limit, coating unevenness and coating defects are likely to occur.

[0189] Such a film-forming resin composition can be obtained by a suitable method such as kneading the above-mentioned materials.

[0190] The viscosity of the film-forming resin composition is preferably 20 to 100,000 cps / 20° C., more preferably 20 to 80,000 cps / 20° C., and even more preferably 20 to 12,000 cps / 20° C. When the viscosity of the film-forming resin composition is within this range, the leveling property during film formation is improved, making it easier to achieve a uniform film thickness.

[0191] As the resin composition for film formation, from the viewpoint of ensuring high oxygen permeability, urethane-based resins and silicone-based resins are preferably used. In order to increase adhesion, a tacky resin may be added.

[0192] Examples of urethane-based resins that can be used include "Asaflex 825" (manufactured by Asahi Kasei Corporation), "Pellethene 2363-80A", "Pellethene 2363-80AE", "Pellethene 2363-90A", and "Pellethene 2363-90AE" (all manufactured by The Dow Chemical Company), and "Heimullen Y-237NS" (manufactured by Dainichiseika Color & Chemicals Co., Ltd.).

[0193] The silicone resin or silicone polymer, or the silicone resin composition for obtaining them, may be blended or composed without any particular limitation. The monomer used in the silicone resin composition may be monofunctional, difunctional, trifunctional, or tetrafunctional, and may be used alone or in combination of two or more kinds. The monomer may be a halogenated alkylsilane, an unsaturated silane, an aminosilane, a mercaptosilane, or an epoxysilane. Examples of the monomer that may be used include HSiCl3, SiCl4, MeSiHCl2, Me3SiCl, MeSiCl3, Me2SiCl2, Me2HSiCl, PhSiCl3, Ph2SiCl2, MePhSiCl2, Ph2MeSiCl, CH2=CHSiCl3, Me(CH2=CH)SiCl2, Me2(CH2=CH)SiCl, (CF3CH2CH2)MeSiCl. 2、 (CF3CH2CH2)SiCl3, CH 18 H 37Examples of monomers represented by the chemical formula SiCl3 (in the chemical formula, "=" represents a double bond, "Me" represents a methyl group, and "Ph" represents a phenyl group) can be mentioned. The monomers may be used alone or in combination of two or more. As other organic groups, alkyl groups such as propyl group, isopropyl group, butyl group, isobutyl group, tert-butyl group, hexyl group, octyl group, and decyl group; aryl groups such as phenyl group, tolyl group, xylyl group, and naphthyl group; cycloalkyl groups such as cyclopentyl group and cyclohexyl group; and aralkyl groups such as benzyl group, 2-phenylethyl group, and 3-phenylpropyl group may be used. Among these, methyl group, phenyl group, or a combination of both are preferred. This is because the components that are methyl group, phenyl group, or a combination of both are easy to synthesize and have good chemical stability. In addition, when a polyorganosiloxane with particularly good solvent resistance is to be used, a combination of methyl group, phenyl group, or a combination of both and 3,3,3-trifluoropropyl group is preferred.

[0194] The silicone resin composition may contain an organoalkoxysilane. Examples of the organoalkoxysilane include Me3SiOCH3, Me2Si(OCH3)2, MeSi(OCH3)3, Si(OCH3)4, Me(C2H5)Si(OCH3)2, C2H5Si(OCH3)3, and C 10 H 21 Examples of the compounds represented by the chemical formulas include Si(OCH3)3, PhSi(OCH3)3, Ph2Si(OCH3)2, MeSiOC2H5, Me2Si(OC2H5)2, Si(OC2H5)4, C2H5Si(OC2H5)3, PhSi(OC2H5)3, and Ph2Si(OC2H5)2. These may be used alone or in combination of two or more.

[0195] Furthermore, the silicone resin composition may contain an organosilanol. Examples of organosilanol include compounds represented by chemical formulas such as Me3SiOH, Me2Si(OH)2, MePhSi(OH)2, (C2H5)3SiOH, Ph2Si(OH)2, and Ph3SiOH. These may be used alone or in combination of two or more.

[0196] In order to obtain a silicone polymer used in a silicone resin, it is also preferable to utilize reactions such as hydrolysis of chlorosilanes and ring-opening polymerization of cyclic dimethylsiloxane oligomers. Examples of the polymer used in this case include one or more selected from the group consisting of dimethyl polymers, methylvinyl polymers, methylphenylvinyl polymers, and methylfluoroalkyl polymers.

[0197] The method for curing the silicone polymer, i.e., the method for obtaining a silicone resin by reacting (vulcanizing) is not particularly limited, and examples thereof include heat vulcanization and room temperature vulcanization. Either a millable type silicone resin composition or a liquid rubber type silicone resin composition can be used as the state before the reaction. The polymer used in the millable type silicone resin composition is preferably a polymer with a degree of polymerization of about 4000 to 10000, and may be of one-liquid type or two-liquid type. Examples of the reaction method include dehydration condensation between silanol groups (Si-OH). Reactions that may be used include condensation reactions between silanol groups and hydrolyzable groups, reactions of methylsilyl groups (Si-CH3) and vinylsilyl groups (Si-CH=CH2) with organic peroxides, addition reactions of vinylsilyl groups and hydrosilyl groups (Si-H), reactions with ultraviolet light, and reactions with electron beams.

[0198] (Dehydration condensation reaction between silanol groups) The catalyst used may be one or more selected from the group consisting of zinc octylate, iron octylate, organic acid salts of cobalt and tin, and amine catalysts, and the reaction may be carried out by heating.

[0199] (Condensation reaction between silanol groups and hydrolyzable groups) As a catalyst, an acid, an alkali, an organic tin compound, an organic titanium compound, etc. may be added. As a hydrolyzable group, an alkoxy group, an acetoxy group, an oxime group, an aminoxy group, a propenoxy group, etc. may be used.

[0200] (Reaction of methylsilyl and vinylsilyl groups with organic peroxides) As a peroxide curing agent for accelerating the reaction, an organic peroxide, an acyl-based organic peroxide, an alkyl-based organic peroxide, or the like may be added. As an acyl-based organic peroxide, for example, p-methylbenzoyl peroxide, or the like may be used. As an alkyl-based organic peroxide, for example, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, dicumyl peroxide, or the like may be used. The reaction temperature is, for example, 120°C or higher, and secondary vulcanization (post-cure) may be performed. The amount of peroxide curing agent added is preferably 0.1 to 10% by mass based on the solid content of the resin.

[0201] (Addition reaction of alkenyl group with hydrosilyl group) For example, a vinyl group is preferably used as the alkenyl group. The reaction temperature may be room temperature or may be heated. The reaction may be carried out in an open system or in a closed system. In the process of obtaining a composition used in the addition reaction between an alkenyl group and a hydrosilyl group, an additive for removing an organic compound containing nitrogen, phosphorus, sulfur, etc., an ionic compound of a metal such as tin or lead, a compound having an unsaturated group such as acetylene, alcohol, water, or a carboxylic acid may be added or a process of removing the same may be used. When the addition reaction between an alkenyl group and a hydrosilyl group is used, a polysiloxane or hydrogen polysiloxane having a vinyl group is preferably used. As the polysiloxane having a vinyl group, a linear polysiloxane having a viscosity of 1 to 100,000 mPa·s at 23° C. is preferably used. The polysiloxane contains one or more vinyl groups in one molecule. Specific examples of polysiloxanes having vinyl groups include dimethylsiloxane-methylvinylsiloxane copolymers capped with trimethylsiloxy groups at both molecular chain ends, methylvinylpolysiloxane capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped with trimethylsiloxy groups at both molecular chain ends, dimethylpolysiloxane capped with dimethylvinylsiloxy groups at both molecular chain ends, methylvinylpolysiloxane capped with dimethylvinylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylvinylsiloxane copolymers capped with dimethylvinylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped with dimethylvinylsiloxy groups at both molecular chain ends, dimethylpolysiloxane capped with trivinylsiloxy groups at both molecular chain ends, etc. These polysiloxanes may be used alone or in combination of two or more.

[0202] The hydrogen polysiloxane is preferably a linear polysiloxane having a viscosity of 1 to 100,000 mPa·s at 23°C. The hydrogen polysiloxane contains one or more hydrogen atoms bonded to silicon atoms in one molecule. Specific examples of hydrogen polysiloxane include those having hydrogen atoms at both ends of the molecular chain as long as the viscosity at 23°C is 1 to 100,000 mPa·s. Examples of such compounds include dimethylpolysiloxane blocked with dimethylhydrogensiloxy groups, dimethylpolysiloxane blocked with diphenylhydrogensiloxy groups at both molecular chain terminals, methylphenylpolysiloxane blocked with dimethylhydrogensiloxy groups at both molecular chain terminals, diphenylpolysiloxane blocked with dimethylhydrogensiloxy groups at both molecular chain terminals, methylphenylsiloxane-dimethylsiloxane copolymer blocked with dimethylhydrogensiloxy groups at both molecular chain terminals, diphenylsiloxane-dimethylsiloxane copolymer blocked with dimethylhydrogensiloxy groups at both molecular chain terminals, and mixtures of two or more of these compounds.

[0203] In the resin composition used in the addition reaction of alkenyl groups with hydrosilyl groups, the molar ratio of hydrogen atoms bonded to silicon atoms to alkenyl groups is preferably 0.01 to 20 mol, more preferably 1 to 2 mol.

[0204] As the reaction catalyst, for example, platinum group metals such as platinum, palladium, and rhodium can be used, and platinum compounds such as chloroplatinic acid, alcohol-modified chloroplatinic acid, and coordination compounds of chloroplatinic acid with olefins, vinylsiloxane, or acetylene compounds, platinum group metal compounds such as tetrakis(triphenylphosphine)palladium, chlorotris(triphenylphosphine)rhodium, etc. can be used. In addition, since compatibility with silicone oil is required, platinum compounds obtained by modifying chloroplatinic acid with silicone are preferably used. When using a catalyst, the amount of addition calculated from the solid content mass is preferably 0.01 ppm to 10,000 ppm, and more preferably 0.1 ppm to 1,000 ppm.

[0205] The total amount of hydrosilyl groups is usually 0.01 to 20 moles, preferably 0.1 to 10 moles, per mole of alkenyl groups bonded to silicon atoms in the entire silicone resin composition. If the total amount is less than the lower limit of the above range, the resulting silicone resin composition tends to be difficult to cure sufficiently, and if it exceeds the upper limit of the above range, the mechanical properties and heat resistance of the cured product of the resulting silicone resin composition tend to be easily reduced. Reaction inhibitors are added to prevent thickening or gelation before curing when silicone resins are mixed or when they are applied to a substrate, etc. Examples of reaction inhibitors include low molecular weight polysiloxanes with multiple alkenyl groups and acetylene alcohol-based compounds.

[0206] (Reaction caused by ultraviolet light) Examples of ultraviolet-curable silicone resins that can be used include radical reaction types (acrylic and mercapto types), combined radical reaction / condensation reaction types (mercapto / isopropenoxy and acrylic / alkoxy types), and addition reaction types that use an ultraviolet-active platinum catalyst. In the acrylic radical reaction type, an organic group having an acrylic group bonded to a siloxane is subjected to a radical polymerization reaction in the presence of a photosensitizer.

[0207] In the mercapto type radical reaction type, an organic group having a mercapto group bonded to a siloxane and a polysiloxane having a vinyl group are subjected to a radical addition reaction in the presence of a photosensitizer. As a catalyst used in the addition reaction type using a platinum catalyst active under ultraviolet light, (methylcyclopentadienyl)trimethylplatinum complex, bisacetylacetonatoplatinum(II) complex, etc. are used, and it is preferable to cure with a light source having a wavelength of around 365 nm. As the main functional group used in the photocuring reaction, an acrylic group or an epoxy group may be used. A photoinitiator may be used in the composition used for the reaction by ultraviolet light.

[0208] (Method of imparting adhesiveness to silicone resin) A suitable method for imparting adhesiveness to silicone resins is, for example, the addition of a silicone polymer that imparts adhesiveness. A suitable silicone polymer that imparts adhesiveness is, for example, MQ resin. MQ resin is a monomer having one functional group (M It is a polymer having a three-dimensional structure synthesized from a monomer having four functional groups (Q units) and a monomer having four functional groups (Q units). The molecular weight of the polymer having the three-dimensional structure is preferably 10 to 100,000, more preferably 100 to 10,000. As the organic group of the monomer having each functional group, a methyl group is preferably used, but in the case of an addition reaction type silicone resin, an alkenyl group is preferably used. The content of the MQ resin in the silicone resin is preferably 10 to 99 mass% in terms of solid content, more preferably 20 to 80 mass%, from the viewpoint of achieving both strength and adhesiveness of the silicone resin. In the present invention, when obtaining a silicone polymer that imparts adhesiveness, a monomer having two functional groups (D units) or a monomer having three functional groups (T units) may be added as appropriate, and a monomer or oligomer having other functional groups may be added.

[0209] The MQ resin preferably has a structure in which the ends of a condensation product of Q units are blocked with M units. From the viewpoint of achieving both adhesiveness and strength of the silicone resin, the molar ratio of M units to Q units is preferably 0.4 to 1.2, and more preferably 0.6 to 0.9.

[0210] Additives may be added in the process of obtaining silicone polymers and silicone resins from silicone monomers. Examples of additives include reinforcing agents (silica fillers such as dry silica and wet silica), dispersants, adhesion aids (silane coupling agents, etc.), adhesion promoters (organic metal compounds, etc.), reaction regulators, extenders (crystalline silica, calcium carbonate, talc, etc.), heat resistance improvers (iron oxide, cerium oxide, titanium oxide, etc.), flame retardants (titanium oxide, carbon, etc.), thermally conductive fillers, conductive agents, surface treatment agents, pigments, dyes, or rare earths, titanium, zircon, manganese, iron, cobalt, nickel, and other metal oxides, hydroxides, carbonates, and fatty acid salts.

[0211] As the silica filler, for example, a known fine powder silica can be used. The fine powder silica may be hydrophilic or hydrophobic. Examples of the hydrophilic fine powder silica include wet silica such as precipitated silica, and dry silica such as silica xerogel and fumed silica. Examples of the hydrophobic fine powder silica include fine powder silica obtained by hydrophobizing the surface of hydrophilic fine powder silica. Examples of the hydrophobizing agent include organosilazanes such as hexamethyldisilazane; halogenated silanes such as methyltrichlorosilane, dimethyldichlorosilane, and trimethylchlorosilane; and organoalkoxysilanes in which the halogen atom of the halogenated silane is substituted with an alkoxy group such as a methoxy group or an ethoxy group. Examples of the hydrophobizing method include a method in which hydrophilic fine powder silica is heat-treated with a hydrophobizing agent at 150 to 200°C, particularly at 150 to 180°C, for about 2 to 4 hours. The hydrophobic fine powdered silica obtained by previously hydrophobizing the surface of the hydrophilic fine powdered silica in this manner may be blended into a film-forming resin composition, or a hydrophobizing treatment agent may be blended into the film-forming resin composition together with the hydrophilic fine powdered silica, so that the surface of the hydrophilic fine powdered silica is hydrophobized at the stage of preparing the film-forming resin composition.

[0212] Specific examples of silica fillers include hydrophilic finely powdered silica such as Aerosil (registered trademark) 50, 130, 200 and 300 (trade names, manufactured by Nippon Aerosil Co., Ltd.), Cabosil (registered trademark) MS-5 and MS-7 (trade names, manufactured by Cabot Corporation), Reolosil QS-102 and 103 (trade names, manufactured by Tokuyama Corporation), and Nipsil LP (trade name, manufactured by Nippon Silica Co., Ltd.); and hydrophobic finely powdered silica such as Aerosil (registered trademark) R-812, R-812S, R-972 and R-974 (trade names, manufactured by Degussa Co., Ltd.), Reolosil MT-10 (trade name, manufactured by Tokuyama Corporation), and Nipsil SS series (trade names, manufactured by Nippon Silica Co., Ltd.).

[0213] When finely powdered silica is used, the blending amount is usually 1 to 50 mass% calculated as solid content. When the blending amount is 1 mass% or more, the silica filler can provide a sufficient strength-imparting effect, and when the blending amount is 50 mass% or less, the obtained silicone resin composition can have sufficient fluidity, and as a result, excellent workability can be ensured.

[0214] As the adhesion promoter, for example, an organic titanium compound, such as an organic acid salt of titanium, can be used. The adhesion promoter can be used as a catalyst to further accelerate the curing of the silicone resin composition and further improve its adhesiveness. The adhesion promoter can be used alone or in combination of two or more kinds.

[0215] Examples of the adhesion promoter include titanium chelate compounds, alkoxy titanium, and combinations thereof. Specific examples of titanium chelate compounds include diisopropoxy bis(acetylacetonato) titanium, diisopropoxy bis(ethylacetoacetato) titanium, dibutoxy bis(methylacetoacetato) titanium, and the like. Specific examples of alkoxy titanium include tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, and the like. The alkoxy group in the alkoxy titanium may be linear or branched.

[0216] The amount of the adhesion promoter is preferably 0.01 to 10 mass %, more preferably 0.1 to 5 mass %, calculated as solid content. When the amount is equal to or more than the lower limit of the above range, the adhesiveness improving effect is easily achieved, and when the amount is equal to or less than the upper limit of the above range, the surface curing of the resulting film-forming resin composition can be prevented from becoming too rapid.

[0217] Silane coupling agents are compounds that have an alkoxy group bonded to a silicon atom and a reactive group that chemically bonds with an adherend such as a metal or various synthetic resins in one molecule, and compounds that have an alkenyl group or a hydrogen atom may be used instead of the alkoxy group bonded to the silicon atom. Epoxy groups or acrylic groups may be used as the reactive group that chemically bonds with the adherend.

[0218] When applying a silicone resin, a primer may be applied to the material to be applied before application. As the primer, a silicone resin of a condensation curing type, an addition curing type, or the like can be used. The amount of primer applied is 0.1 to 1.2 g / m 2 is preferred.

[0219] Examples of silicone resins include "SYLGRAD186", "DOWSIL3-6512", "SYLGRAD527", "DOWSILX3-6211", "SYLGRAD3-6636", "DOWSIL SE1880", "DOWSIL SE960", "DOWSIL781 Acetoxy Silicone", "DOW CORNING SE9187", "DOWSIL Q1-4010", "SYLGRAD 1-4128", "DOWSIL 3140 RTV Coating", "DOWSIL HC2100", "SIL-OFF Q2-7785", "Silaseal 3FW", "Silaseal DC738RTV", "DC3145", and "DC3140" (all manufactured by Dow Corning Corporation), "ELASTOSIL RT707W", "ELASTOSIL EL4300", "ELASTOSIL M4400", "ELASTOSIL M8012", and "SILRES BS CREME C”, “SILRES BS 1001”, “SILRES BS 290”, “ELASTSIL 912”, “ELASTSIL E43N”, “ELASTOSIL N9111”, “ELASTOSIL N199”, “SEMICOSIL 987GR”, “ELASTOSIL RT772”, “ELASTOSIL RT745”, “ELASTOSIL LR3003 / 05", "ELASTOSIL LR3343 / 40", "ELASTOSIL LR3370 / 40", "ELASTOSIL LR3374 / 50BR", "ELASTOSIL EL1301", "ELASTOSIL EL 4406", "ELASTOSIL EL3530", "ELASTOSIL EL 7152”, “ELASTOSIL R401 / 10OH”, “SILPUREN 21XX series" (manufactured by Asahi Kasei Wacker Silicone Co., Ltd.), "KE-3423", "KE-347", "KE-3479", "KE-1830", "KE- 1820'', ``KE-1056'', ``KE-1800T'', ``KE-66'', ``KE-1031'', ``KE-12'', ``KE-1300T'', ``SD4584PSA'', ``KS-847T'', ``KF-2005'', ``KNS-3''. 002", "KR-100", "KR-101-10", "KR-130", "KR-3600", "KR-3704", "KR-3700", "KR-3701", "X-40-3237", "X-40-3291-1", "X -40-3240", "Sealant 45", "Sealant Master 300", "Sealant 72", "KE-42", "Sealant 70", "KE-931-U", "KE-9511-U", "KE-541-U", "KE-153-U", "KE-361-U", "KE-1950-10", "KEG-2000-40", "KE-2019-40", "KE-2090-50", "KE-2096-60" (manufactured by Shin-Etsu Chemical Co., Ltd.) and the like can be used. A catalyst may be further added to the silicone-based resin. As the catalyst, organic acid salts such as zinc octylate, iron octylate, cobalt, and tin, and amine-based catalysts can be used. In addition, organic tin compounds, organic titanium compounds, and platinum compounds can also be used. As the catalyst, for example, "CAT-PL-50T" (manufactured by Shin-Etsu Chemical Co., Ltd.) and "NC-25" (manufactured by Toray Dow Corning Co., Ltd.) can be used. In addition, when applying, a solvent such as toluene, xylene, or alcohols may be added. Primers that can be used include "Primer AQ-1", "Primer C", "Primer MT", "Primer T", "Primer D", "Primer A-10", "Primer R-3", and "Primer A-20" (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0220] The thickness of the gas-permeable non-porous layer 212 (membrane for water treatment) formed is preferably 5 to 100 μm, and more preferably 10 to 90 μm, in consideration of achieving both oxygen permeability and waterproofness.

[0221] By making the thickness of the gas-permeable non-porous layer 212 5 μm or more, the risk of the gas-permeable non-porous layer 212 breaking is reduced even in a situation where high water pressure is applied to the gas-permeable non-porous layer 212. On the other hand, by making the thickness of the gas-permeable non-porous layer 212 100 μm or less, sufficient oxygen permeability is maintained, and as a result, sufficient wastewater treatment function can be ensured. In this specification, the thickness of the gas-permeable non-porous layer 212 is defined as the thickness according to JIS1913:2010 General Nonwoven Fabric Test Method 6.1 Thickness. It is defined as the value measured by the method for measuring the thickness.

[0222] (base material) The sheet laminate 81 may be produced by immersing, multi-layer extrusion, coating, or laminating the film-forming resin composition on the substrate 211. The substrate 211 is not particularly limited as long as it is permeable to oxygen and the like, and any known substrate may be widely used. Specifically, it is preferable to use one or more selected from the group consisting of a microporous membrane, a porous sheet, and a non-porous membrane with high oxygen permeability. If the substrate 211 does not have gas permeability, sufficient oxygen cannot be delivered to the biofilm 214, and as a result, a stable biofilm 214 cannot be formed.

[0223] Hereinafter, the third embodiment of the present invention will be described in more detail based on examples, but the present invention is not limited to these.

[0224] (Example 17) The substrate is a microporous membrane of Sumika Sekisui Film Co., Ltd.'s Cellpore NW07H, with a reinforcing layer on one side and A substrate (thickness 150 μm) (1) was prepared by thermally laminating the polyethylene and polyester nonwoven fabric used in NW07H. Next, an additional hardener with a solid content of 60 mass% was applied. A mixture of 70 parts by mass of an addition-curing silicone adhesive stock solution (product name SD-4560, manufactured by Dow Corning Toray Co., Ltd.) and 30 parts by mass of an addition-curing silicone adhesive stock solution (product name SD-4587L, manufactured by Dow Corning Toray Co., Ltd.) with a solid content concentration of 40% by mass and toluene as a dilution solvent was used. 54 parts by mass of ethylenediaminetetraacetate and 0.3 parts by mass of a platinum catalyst (product name NC-25, manufactured by Dow Corning Toray Co., Ltd.) as a curing catalyst were uniformly mixed to obtain a film-forming resin composition (2). 1) Apply to the non-laminated surface of the non-woven fabric, then leave in an atmosphere of 130℃ for 30 minutes. After curing, a membrane with a thickness of 180 μm was obtained. After curing, Elves II (30 g / m 2 ) (manufactured by Unitika Ltd.) was laminated thereon to obtain a sheet laminate of Example 17.

[0225] (Example 18) A sheet laminate was obtained in the same manner as in Example 17, except that Elbes II was not laminated.

[0226] Comparative Example 3 Non-adhesive silicone sheet (As One, ultra-thin silicone sheet, product number 3-3066-01) A laminate of sheets (0.1 mm thick) was used.

[0227] Comparative Example 4 99 parts by mass of a curable silicone resin (KS-847H manufactured by Shin-Etsu Chemical Co., Ltd.) was applied to the film surface (the surface not laminated with the nonwoven fabric) of the substrate (1) used in Example 17. A mixture was obtained by adding 1 part by mass of a curing agent (PL-50T manufactured by Shin-Etsu Chemical Co., Ltd.) to the mixture. The mixture was adjusted to 2% by mass using a toluene / MEK mixed solvent (mixing ratio 1:1), and applied using a bar coater. Then, it was heated and dried at 140° C. for 1 minute to obtain a sheet laminate with a total thickness of 180 μm.

[0228] Based on the above formulation, film-forming resin compositions of the respective Examples and Comparative Examples were obtained.

[0229] [Table 2]

[0230] [Table 3]

[0231] In each of the Examples and Comparative Examples, the peeling of the biofilm was evaluated.

[0232] (Wastewater treatment performance test) The sheet laminate was placed on one vertical side of a cube with an inner dimension of 7 cm, and a sealed evaluation tank was used. The surface of the evaluation tank facing the sheet laminate was made of a transparent PVC material with a thickness of 1 mm. The other surfaces were made of PVC material with a thickness of 10 mm. A polypropylene mesh (Crown Net 24 Mesh, manufactured by Daio Kasei Co., Ltd.) was laminated on the air side of the sheet laminate in order to prevent deformation of the sheet laminate due to water pressure. The evaluation tank was filled with organic matter-containing water of the following composition, and 5 g of paddy field soil, which is soil containing microorganisms as microorganisms responsible for decomposing organic matter, was added. Here, the mass of the paddy field soil is defined as the mass after centrifuging an aqueous dispersion of the paddy field soil and discarding the supernatant. The evaluation tank was placed in a thermostatic tank maintained at 30±2°C, and was left to stand under conditions of continuous stirring using a stirrer. The stirrer was manufactured by AS ONE Co., Ltd. The magnetic stirrer B-1 and the magnetic stirrer CB-4 were used, and the controller scale was set to 4. The power supply frequency was 60 Hz. One rotor (made of PTFE resin) manufactured by AS ONE, length 30 x φ8 mm, was used. The power supply frequency was 60 Hz. Every 3.5 days, the evaluation chamber was removed from the thermostatic chamber and all the liquid in the evaluation chamber was drained. The organic matter-containing water was then replaced and this process was continued for 70 days. (That is, the process of "agitating the organic matter-containing water for 3.5 days → discharging the organic matter-containing water from the evaluation tank → pouring the organic matter-containing water into the evaluation tank" was repeated.) After this, the evaluation tank was filled with the organic matter-containing water and the CODCr concentration was measured. If the CODCr concentration before treatment is A (mg / L) and the CODCr concentration after 3.5 days is B (mg / L), the organic matter removal rate R can be calculated from the following formula (4).

[0233] [Formula 4] R = (1-B / A) x 100 The evaluation tank had a drain outlet with an inner diameter of 2 cm at the top, and the liquid could be drained by turning the evaluation tank upside down vertically. The organic matter removal rate R obtained from the wastewater treatment performance test was defined as 80% or more on the 30th and 70th days, which means that the sheet laminate has the ability to maintain stable treatment performance.) (In Table 3, the organic matter removal rates R on the 8th, 30th, and 70th days are listed in the treatment status column, with 80% or more marked as ◯ and 79% or less marked as △.)

[0234] (Composition of organic matter-containing water) Soluble starch: 0.8 g / L, peptone: 0.084 g / L, yeast extract: 0.4 g / L, urea: 0.052 g / L, CaCl2: 0.055 g / L, KH2PO4: 0.017 g / L, MgSO4·7H2O: 0.001 g / L, KCl: 0.07 g / L, NaHCO3: 0.029 g / L. Tap water from the Kyoto Research Laboratory of Sekisui Chemical Co., Ltd. was used as the solvent.

[0235] (Evaluation of biofilm retention) The biofilm retention was evaluated every time the wastewater was exchanged using the effluent obtained by turning the evaluation tank upside down vertically in the wastewater treatment performance test. The biofilm retention was evaluated using the suspended solids concentration SC (mg / L) of the effluent. The suspended solids concentration SC was calculated using formula (5) from the amount of suspended solids SW (mg) in the effluent and the volume V (L) of the effluent.

[0236] [Formula 5] SC=SW / V

[0237] The suspended solids amount SW was measured according to the method described in JIS K 0102:2013 Industrial Wastewater Testing Method, Section 14.1, and the filter material used in the measurement was Advantec Toyo Glass Filter Paper (product number G25, diameter 47 mm). When the suspended solids concentration SC was 100 mg / L or more three times or more during the measurement period of 70 days in the wastewater treatment performance test, the biofilm retention was defined as low.

[0238] (evaluation) In Examples 17 and 18, the number of times that the suspended solids concentration SC was 100 mg / L or more was less than three times over the entire measurement period of 70 days. Therefore, stable retention of biofilm was confirmed in Examples 17 and 18. Stable treatment was also confirmed in the wastewater treatment performance test.

[0239] In Comparative Examples 3 and 4, which are non-adhesive sheet laminates, the suspended solids concentration SC was 100 mg / L or more three times over the entire measurement period of 70 days, biofilm peeling was confirmed in many cases, and the amount of microbial adhesion on the surface was sparse and uneven. When sheet laminates such as those in Comparative Examples 3 and 4 are used in wastewater treatment equipment, there is a concern that the biofilm will peel off, leading to an increase in excess sludge, and that clumped biofilms will clog the piping or between membranes of the wastewater treatment equipment, causing blockages. From the above, adding an adhesive component to the surface is effective in stabilizing the biofilm on the sheet surface.

[0240] [Table 4]

[0241] (Embodiment 4) Next, a fourth embodiment of the present invention will be described.

[0242] Although not shown in the figures, in the fourth embodiment, the gas supplier includes a gas-delivery layer and a sheet stack, and the gas-delivery layer is disposed in a bag formed by the sheet stack. The gas-delivery layer is, for example, one of those shown in Figures 5, 12, and 13.

[0243] The sheet laminate of the fourth embodiment is, for example, similar to the sheet laminate 21 shown in Fig. 4, in which the microorganism support layer 213, the substrate 211, and the gas permeable non-porous layer 212 are laminated in this order from the side in contact with wastewater. Alternatively, the sheet laminate of the fourth embodiment is, for example, similar to the sheet laminate 81 shown in Fig. 14, in which the microorganism support layer 213, the gas permeable non-porous layer 212, and the substrate 211 are laminated in this order from the side in contact with wastewater.

[0244] In the fourth embodiment, in order to reduce the deterioration of the wastewater treatment function that occurs with use, the sheet laminate has a microbial adhesion index MA calculated by the following formula (6) of 0.08 or more.

[0245] [Formula 6] MA = W × Q 2.8 ×10 -6 [W: basis weight of the microbial support layer (g / m 2 ), Q: oxygen permeability (g / (m 2 d))

[0246] (microbial support layer) The microbial support layer can be formed by a known method using the material shown in the first embodiment in the above-mentioned manner. In particular, it is preferable to form the microbial support layer by surface treatment of the porous substrate. By adopting such a method, it is possible to improve the roughness and zeta potential of the porous substrate surface by surface treatment, and as a result, the microbial adhesion is improved.

[0247] For example, the surface treatment may be carried out by graft polymerizing glycidyl methacrylate and then reacting with diethylamine or sodium sulfite. Alternatively, the surface treatment may be carried out by graft polymerizing glycidyl methacrylate and then reacting with ammonia or ethylamine. It is also preferred to react the compound with ethylamine.

[0248] In addition, when forming the microbial support layer, a material having polarity may be added to the porous substrate. In this specification, a resin having polarity is defined as a resin having one or more functional groups selected from the group consisting of a hydroxyl group, an aldehyde group, a carboxyl group, a carbonyl group, an amino group, a nitro group, a sulfo group, an ether bond, and an ester bond in its composition. By adding a material having polarity to the porous substrate, it is possible to obtain the effect of making it easier for microorganisms to adhere.

[0249] The sheet laminate of embodiment 4 has a biofilm thickness of 1 mm or more and 5 mm or less when measured under the following biofilm evaluation conditions. Note that when the sheet laminate of embodiment 4 is used and measured under the measurement conditions, a biofilm of 1 mm or more and 5 mm or less is formed. (Biofilm evaluation conditions) (1) The sheet laminate is placed on one vertical side of a cube with an inner dimension of 7 cm, and the sealed evaluation chamber is filled with organic matter-containing water of the following composition. (2) (Composition of the above organic matter-containing water) Soluble starch: 0.8 g / L, peptone: 0.084 g / L, yeast extract: 0.4 g / L, urea: 0.052 g / L, CaCl2: 0.055 g / L, KH2PO4: 0.017 g / L, MgSO4·7H2O: 0.001 g / L, KCl: 0.07 g / L, NaHCO3: 0.029 g / L. The solvent was tap water. (3) 5 g of paddy field soil containing microorganisms responsible for decomposing organic matter was added, and the evaluation chamber was placed in a thermostatic chamber maintained at 30±2°C and continuously stirred using a stirrer. Under these conditions, the liquid in the evaluation tank is completely discharged every 3.5 days. (4) After the organic matter-containing water was replaced for 28 days, the organic matter-containing water was filled into the evaluation tank (time Ta), and after 3 days (time Tb), the sheet laminate was Here, the mass of the paddy field soil is defined as the mass after centrifuging the aqueous dispersion of the paddy field soil and discarding the supernatant.

[0250] By forming a sheet laminate having a biofilm thickness of 1 mm to 5 mm when measured under the above biofilm evaluation conditions, the biofilm does not peel off and is maintained at an appropriate thickness even when exposed to a high flow rate during use of the MABR. In addition, since the biofilm is maintained at an appropriate thickness, aeration is not required, suppressing the generation of excess sludge and the decrease in treatment performance due to the biofilm falling off. In addition, brushing or the like for controlling the biofilm thickness is not required, suppressing damage to the membrane. Furthermore, peeling of the biofilm due to fluctuations in flow rate and flow rate, bias in flow rate, and maintenance such as draining the tank can be prevented, allowing appropriate treatment to be performed.

[0251] In addition, the sheet laminate of the fourth embodiment has a thickness of 10 g / (m 2 It is preferable to use a sheet laminate having an oxygen permeability of at least d). By adopting such a configuration, it is possible not only to set the thickness of the biofilm within the above-mentioned numerical range, but also to allow oxygen to be distributed appropriately, enabling treatment by aerobic microorganisms and preventing the wastewater treatment from switching to anaerobic microorganisms that do not require oxygen, thereby making it possible to suppress the generation of harmful gases such as hydrogen sulfide from the wastewater in the wastewater treatment device and the odors caused by such gases.

[0252] In addition, the oxygen permeability of the sheet laminate was 25 g / (m 2 It is more preferable to set the oxygen permeability to 25 g / (m 2 By setting the concentration to d) or more, it is possible to prevent the area near the microbial support layer from becoming aerobic, thereby preventing an increase in the proportion of anaerobic microorganisms. As a result, the adhesion of the biofilm to the microbial support layer is maintained, and the biofilm is less likely to peel off.

[0253] Generally, microbial carriers that are not oxygen permeable tend to have an increased ratio of anaerobic microorganisms near the carrier. In order to increase the amount of oxygen, the process switches to anaerobic treatment, and methane and hydrogen sulfide are discharged. Furthermore, since aerobic microorganisms require oxygen, if oxygen is not available, the ratio of aerobic microorganisms in the biofilm decreases, and the biofilm becomes more likely to peel off. Furthermore, oxygen can be supplied to the wastewater by aeration or the like to improve the treatment performance, but when oxygen is supplied to the wastewater using a sheet laminate with low oxygen permeability, the treatment performance may decrease. That is, in the above cases, the biofilm may become too thick and peel off, the flow path may be blocked by the biofilm, causing a short pass, or the effective surface area of ​​the sheet may decrease, resulting in a decrease in treatment performance.

[0254] More preferably, the microbial adhesion index MA, represented by the following formula (7), is set to 0.08 or more, so that the thickness of the biofilm can be set to 1 mm or more and 5 mm or less.

[0255] [Formula 7] MA = W × Q 2.8 ×10 -6 [W: basis weight of the microbial support layer (g / m 2 ), Q: oxygen permeability (g / (m 2 d))

[0256] In the fourth embodiment, the oxygen permeability Q means the oxygen permeability of the sheet laminate, and is defined as the value obtained by the (oxygen supply test) shown in the first embodiment.

[0257] In the fourth embodiment, the thickness of the biofilm means the thickness of the biofilm formed on the surface of the microbial support layer (not including the thickness of the microbial support layer). Regarding the part where the thickness is measured, the thickness is measured at the center of the inscribed circle of the area of ​​the sheet laminate that was in contact with the organic matter-containing water.

[0258] Hereinafter, the fourth embodiment will be described in more detail based on examples, but the present invention is not limited to these.

[0259] (Example 19) As shown in Table 5 below, a polypropylene microporous membrane (pore size 33 μm or less, thickness 120 μm) included in Celpore NW07H manufactured by Sekisui Chemical Co., Ltd. was used as the porous substrate. 2 A nonwoven fabric (Elves II, T0203WDO, manufactured by Unitika) with a thickness of 120 μm and a double structure of a polyester core and a polyethylene sheath was used, and a sheet laminate was obtained by thermal lamination using a hot plate heated to 120°C.

[0260] (Example 20) As the silicone resin composition used to form the gas-permeable non-porous layer, a solution was obtained by uniformly mixing 100 parts by mass of an addition reaction curing type silicone resin (KR-3701) manufactured by Shin-Etsu Silicone Co., Ltd., 0.5 parts by mass of a platinum catalyst (CAT-PL-50T) manufactured by Shin-Etsu Silicone Co., Ltd., and 71 parts by mass of toluene. The silicone resin composition was applied to the surface of the porous substrate opposite the microbial support layer using a bar coater, and then allowed to stand for 10 minutes in an atmosphere at 120°C to form a gas-permeable non-porous layer. The weight of the gas-permeable non-porous layer after curing of the silicone resin compound was 20 g / m 2 , and the thickness was 18 μm.

[0261] Example 21 The weight of the gas-permeable non-porous layer is 100g / m 2 A sheet laminate was obtained in the same manner as in Example 20, except that the thickness was 90 μm.

[0262] Example 22 The weight of the gas-permeable non-porous layer is 40g / m 2 A sheet laminate was obtained in the same manner as in Example 20, except that the thickness of the microorganism support layer was 36 μm, and a polyolefin nonwoven fabric included in the above-mentioned Celpore NW07H was used as the microorganism support layer (Celpore NW07H has a three-layer structure of a nonwoven fabric, a microporous membrane, and a nonwoven fabric. Of these, one of the nonwoven fabrics was used as the microorganism support layer, and a polyolefin microporous membrane with a pore size of 33 μm or less and a thickness of 120 μm was used as the porous substrate). The basis weight of the microorganism support layer was 10 g / m 2, and the thickness was 60 μm.

[0263] (Example 23) The weight of the gas-permeable non-porous layer is 80g / m 2 A sheet laminate was obtained in the same manner as in Example 20, except that the thickness was 72 μm.

[0264] (Example 24) The microbial support layer is a nonwoven fabric (Elves II, T0703WDO, manufactured by Unitika) with a double structure of polyester core and polyethylene sheath, and a basis weight of 70 g / m 2 A sheet laminate was obtained in the same manner as in Example 22, except that the thickness was 260 μm.

[0265] (Example 25) The gas-permeable non-porous layer is made of polyurethane resin (Dainichi Seikagaku Kogyo Co., Ltd., Heimullen Y-237NS) with a basis weight of 10 g / m 2 A sheet laminate was obtained in the same manner as in Example 20, except that the thickness was 7 μm.

[0266] (Example 26) A sheet laminate was obtained in the same manner as in Example 24, except that a substrate made of a polypropylene microporous membrane (manufactured by 3M, microporous film, pore size 0.3 μm or less, thickness 40 μm) was used as the porous substrate.

[0267] Example 27 A sheet laminate was obtained in the same manner as in Example 24, except that a substrate which was a polyolefin microporous membrane (Mitsubishi Plastics, Inc., Excelpol E BSPBX-4, 0.2 μm or less, thickness 23 μm) was used as the porous substrate.

[0268] (Example 28) A polyester resin nonwoven fabric (Toyobo Co., Ltd., Volance 7217P, basis weight 220 g / m) was used as a porous sheet that served as both a porous substrate and a microbial support layer. 2 A gas-permeable non-porous layer was laminated on this in the same manner as in Example 22.

[0269] (Example 29) Gas-permeable non-porous layer with a basis weight of 55g / m 2 A 50 μm thick silicone sheet (Hagitec, silicone rubber sheet, model number 244-6012-01) was used as the microbial support layer. 2 A sheet laminate was obtained using a nonwoven fabric (Elves II, T0203WDO, manufactured by Unitika) with a thickness of 120 μm and a double structure of polyester core and polyethylene sheath. No porous substrate was used. The gas-permeable nonporous layer and the microbial support layer were laminated by bonding the outer periphery with silicone caulking (KE-441, manufactured by Shin-Etsu Silicone Co., Ltd.).

[0270] (Example 30) Gas-permeable non-porous layer with a basis weight of 110g / m 2 A silicone sheet (Hagitec, silicone rubber sheet, model number 244-6012-02) with a thickness of 100 μm was used as the microbial support layer. A nonwoven fabric made of polypropylene and polyester resin (Unicel BT-030E, basis weight 30 g / m) was used as the microbial support layer. 2 , porosity 73.4%, PP / PET=30 / 70) A sheet laminate was obtained. No porous substrate was provided. The gas-permeable non-porous layer and the microbial support layer were laminated by bonding the outer periphery with silicone caulking (KE-441, manufactured by Shin-Etsu Silicone Co., Ltd.).

[0271] Comparative Example 5 Gas-permeable non-porous layer with a basis weight of 5g / m 2 A polyethylene film with a thickness of 5 μm (Askul, HD roll standard bag, 0.005 mm thick) was used as the microbial support layer. A polypropylene polyester resin nonwoven fabric (Unicel, BT-060E, basis weight 60 g / m) was used as the microbial support layer. 2 A sheet laminate was created using this composite (polypropylene / PET = 30 / 70, porosity 67.7%).

[0272] Comparative Example 6 As a microbial support layer, polypropylene and polyester resin nonwoven fabric (Unicel BT-030E, basis weight 30 g / m 2 A sheet laminate was produced in the same manner as in Comparative Example 5, except that a PET film having a porosity of 73.4% and a PP / PET ratio of 30 / 70 was used.

[0273] Comparative Example 7 Gas-permeable non-porous layer with a basis weight of 15g / m 2 A 15 μm-thick polyethylene film (As One, product number 61-7289-21) was used as a microbial support layer, and a nonwoven fabric (Elves II, T0203WDO, manufactured by Unitika) with a double fiber structure of polyester core and polyethylene sheath was used as the microbial support layer to obtain a sheet laminate.

[0274] Comparative Example 8 Gas-permeable non-porous layer with a basis weight of 55g / m 2 A 50 μm thick silicone sheet (Hagitec, silicone rubber sheet, model number 244-6012-01) was used to obtain a sheet laminate. A porous substrate and a microbial support layer were not provided.

[0275] Comparative Example 9 Gas-permeable non-porous layer with a basis weight of 110g / m 2 A sheet laminate was prepared using a 100 μm thick silicone sheet (Hagitec, silicone rubber sheet, model number 244-6012-02). A porous substrate and a microbial support layer were not provided.

[0276] (Biofilm formation evaluation) The sheet laminate was placed on one vertical side of a cube with an inner dimension of 7 cm, and a sealed evaluation tank was used. The surface of the evaluation tank facing the sheet laminate was made of a transparent PVC material with a thickness of 1 mm. The other surfaces were made of PVC material with a thickness of 10 mm. A polypropylene mesh (Crown Net 24 Mesh, manufactured by Daio Kasei Co., Ltd.) was laminated on the air side of the sheet laminate in order to prevent deformation of the sheet laminate due to water pressure. The evaluation tank was filled with organic matter-containing water of the following composition, and 5 g of paddy field soil, which is soil containing microorganisms as microorganisms responsible for decomposing organic matter, was added. The evaluation tank was placed in a thermostatic tank maintained at 30±2°C, and was left to stand under conditions of continuous stirring using a stirrer. The stirrer was a magnetics made by AS ONE Co., Ltd. The controller CB-4 for the stirrer B-1 and the magnetic stirrer B-1 were used, and the scale of the controller was set to 4. The frequency of the power supply was 60 Hz. One rotor (made of PTFE resin) manufactured by AS ONE Corporation, length 30 x φ8 mm, was used. The frequency of the power supply was 60 Hz. The evaluation tank was removed from the thermostatic tank every 3.5 days, all the liquid in the evaluation tank was drained, and the organic matter-containing water was replaced. This operation was continued for 28 days. An outlet with an inner diameter of 2 cm was provided at the top of the evaluation tank, and the liquid was drained by turning the evaluation tank upside down vertically. Next, the organic matter-containing water was filled into the evaluation tank (time Ta), and after 72 hours (time Tb), the sheet laminate was taken out, and the thickness of the biofilm measured at the center point of the area of ​​the sheet laminate that had been in contact with the organic matter-containing water was measured. A standard stop square manufactured by Shinwa Measurement Co., Ltd. was used for the measurement. The biofilm thickness was measured in increments of 0.5 mm, rounded up to the nearest 0.5 mm. The thickness H (mm) was measured. For example, when the square reading was 1.1 mm, the biofilm thickness H was taken as 1.5 mm, and when the square reading was 2.0 mm, the biofilm thickness H was taken as 2.0 mm. (Composition of organic matter-containing water) Soluble starch: 0.8 g / L, peptone: 0.084 g / L, yeast extract: 0.4 g / L, urea: 0.052 g / L, CaCl2: 0.055 g / L, KH2PO4: 0.017 g / L, MgSO4·7H2O: 0.001 g / L, KCl: 0.07 g / L, NaHCO3: 0.029 g / L. Tap water from the Kyoto Research Laboratory of Sekisui Chemical Co., Ltd. was used as the solvent.

[0277] (Organic matter removal rate) R (g / m) is calculated from the CODCr concentration A (g / L) at the time Ta, the CODCr concentration B (g / L) at the time Tb, and the water volume V (L) in the evaluation tank using the following relational expression: 2 ·d) was defined as the organic matter removal rate. R = (AB) × V / (3 × 0.0049) The CODCr concentration was measured using a WTW photoLab7600UV-VIS absorbance water quality meter and VARIO COD measurement reagent LR. The CODCr concentration was measured using the above-mentioned measurement test according to the protocol specified by the product. When the value exceeded the measurement range of the drug, the sample to be measured was diluted with ion-exchanged water so that it fell within the measurement range, and the measured value was multiplied by the dilution factor to obtain the measured CODCr concentration.

[0278] (Oxygen permeability) In the test to confirm oxygen permeability, a sheet was placed on one vertical side of a cube with an inner dimension of 7 cm. A polypropylene mesh (Diamond Chemical Industries, Ltd., Crown Net 24 Mesh) was laminated on the air side of the sheet laminate to prevent deformation of the sheet laminate due to water pressure. A stirrer rotor (As One Corporation, rotor (PTFE resin), length 60 mm, φ8 mm) and ion-exchanged water were placed in the evaluation tank. Sodium sulfite was added to the ion exchange water at 100 mg / L, and cobalt chloride was added at 1.5 mg / L or more. The oxygen concentration in the evaluation tank was continuously measured while stirring was performed using a Koike Precision Machinery Co., Ltd. stirrer "HE-20GB" at a rotation speed of 7 in the HIGH range. The source frequency was 60Hz. The oxygen supply performance was evaluated in an environment of 23 to 27 degrees Celsius. From the time series data of the measured oxygen concentration, the common logarithm Y=log10(Cs-C) of the oxygen deficiency against time t(h) was calculated. An approximate straight line was obtained from the correlation, and the slope Z of Y versus time t of the approximate straight line was calculated. Cs is the saturated oxygen concentration in the liquid phase at the measurement temperature T, and C is the measured oxygen concentration in the liquid phase at the measurement time t. From the slope Z, the oxygen supply rate Q (g / (m 2 d) was calculated according to the following formula (8). .

[0279] [Formula 8] Q=-2.303×24×0.00884×V×Z×(1.028)^(20-T) / S

[0280] (Leak pressure) The tests to check the leak pressure are mainly based on JIS K 6404-7:1999, A21: High water pressure -Leak pressure was measured using a method that was partially modified from the small sample method (dynamic pressure method). The leak pressure is the pressure gauge value when water first appears through the test piece. The differences from the high water pressure small sample method (dynamic pressure method) are listed below. A support nonwoven fabric (Unitika Marix 82607WSO) was placed on the opposite side of the sheet laminate to the side to which water pressure was applied. The water used in the test was ion-exchanged water with 0.3 wt% Allura Red added. The water pressure was increased at a rate of 0.1 MPa per minute.

[0281] [Table 5]

[0282] As shown in Figure 15, when a biofilm formation evaluation was performed using the sheet laminate of the embodiment, no peeling of the biofilm was observed, but when the sheet laminate of the comparative example was used, peeling of the biofilm was confirmed.

[0283] Furthermore, as shown in FIG. 16, when the sheet laminate of each Example was used, stable or excellent organic matter removal performance was confirmed when the organic matter removal treatment was carried out for 31 days, compared to when the sheet laminate of each Comparative Example was used.

[0284] Furthermore, the average value AV of the organic matter removal rate from the 10th day to the 31st day was obtained, and the coefficient of variation CV was calculated. As shown in Table 6 below, the coefficient of variation in the example was 0.03 or less, which was smaller than the coefficient of variation in the comparative example. The coefficient of variation CV was calculated using the following formula (9). In formula (9), n is the number of measurement points, x i is the organic matter removal rate at each measurement point i. When the coefficient of variation exceeds 0.04, the organic matter removal performance is deemed to vary widely.

[0285] [Formula 9] TIFF0007612762000008.tif22144

[0286] [Table 6]

[0287] (Embodiment 5) Next, a fifth embodiment of the present invention will be described.

[0288] Although not shown in the figures, in the fifth embodiment, the gas supplier includes a gas-delivery layer and a sheet stack, and the gas-delivery layer is disposed in a bag formed by the sheet stack. The gas-delivery layer is, for example, one of those shown in Figures 5, 12, and 13.

[0289] The sheet laminate of the fifth embodiment is, for example, similar to the sheet laminate 21 shown in Fig. 4, in which the microorganism support layer 213, the substrate 211, and the gas permeable non-porous layer 212 are laminated in this order from the side in contact with wastewater. Alternatively, the sheet laminate of the fifth embodiment is, for example, similar to the sheet laminate 81 shown in Fig. 14, in which the microorganism support layer 213, the gas permeable non-porous layer 212, and the substrate 211 are laminated in this order from the side in contact with wastewater.

[0290] In this embodiment, in order to maintain the purification performance of the wastewater treatment device in which the gas supply body is disposed for a long period of time, a sheet laminate having a small degree of water leakage (hereinafter, the leakage degree) over a long period of time is applied to the gas supply body. The leakage degree of the sheet laminate is confirmed by a test in which water pressure is applied to the sheet laminate (hereinafter, the water pressure application test). The water pressure application test will be described below.

[0291] (Measuring equipment used in water pressure application tests) 17 to 20 show the measuring device 40 used in the water pressure application test. Fig. 17 is a plan view of the measuring device 40. Fig. 18 is a side view of the measuring device 40. Fig. 19 is a cross-sectional view showing the measuring device 40 in an assembled state. Fig. 20 is a cross-sectional view showing the measuring device 40 in an exploded state.

[0292] The measuring device 40 is capable of applying water pressure to the sheet laminate for a long period of time and includes a first jig 41, a second jig 42, a ferrule clamp 43, a regulator 44, a plate material 45, and a ferrule gasket 47 (illustration of the ferrule clamp 43 is omitted in FIG. 20).

[0293] As shown in Fig. 20, the first jig 41 includes a first annular body 80 and a first closing plate 81. The first annular body 80 and the first closing plate 81 are made of SUS, and the first annular body 80 has an inner diameter of 113 mm. The first closing plate 81 closes an opening at one end of the first annular body 80, and the outer periphery of the first closing plate 81 is welded to one end face of the first annular body 80. During testing, the internal space of the first annular body 80 is filled with liquid L.

[0294] As shown in Fig. 20, the second jig 42 includes a second annular body 85 and a second closure plate 86. The second annular body 85 is made of SUS and has an inner diameter of 113 mm. The second closure plate 86 is a transparent acrylic plate. The second closure plate 86 closes an opening at one end of the second annular body 85, and the outer periphery of the second closure plate 86 is fastened to one end face of the second annular body 85 by a fastener 83. During testing, the internal space of the second annular body 85 is made hollow.

[0295] As shown in FIG. 19, the ferrule clamp 43 is capable of fastening the first jig 41 and the second jig 42 together with the other end face of the first annular body 80 and the other end face of the second annular body 85 facing each other.

[0296] The regulator 44 is attached to the center of the first closure plate 81. The regulator 44 is provided with a valve, and by operating the valve, air can be supplied to the internal space of the first annular body 80, and the air pressure in the internal space of the first annular body 80 can be adjusted.

[0297] 21 is a photograph showing plate material 45. Plate material 45 is a metal disk with an outer diameter of 130 mm and a thickness of 1 mm. In plate material 45, a punching process (hole making) is performed to form a plurality of through holes 60 in a lattice pattern. More specifically, within the inner range of a circle with a diameter of 113 mm, 831 through holes 60 with a diameter of 3 mm are formed in a lattice pattern with a pitch of 4 mm.

[0298] The ferrule gasket 47 is a rubber ring-shaped body having an outer diameter of 155 mm and an inner diameter of 113 mm. As the ferrule gasket 47, GS-C-EPDM-5.5S manufactured by Osaka Sanitary Co., Ltd. can be used.

[0299] The size of the measuring device 40 and the materials of the components thereof described above are merely examples, and may be changed as appropriate.

[0300] (Water pressure application test) When measuring the leak rate of a sheet stack using the above-mentioned measuring device 40, first, a fastening step is performed in which the outer periphery of the sheet stack and the outer periphery of the plate material 45 are sandwiched between the other end face of the first annular body 80 and the other end face of the second annular body 85, and the first jig 41 and the second jig 42 are fastened by the clamp 43 (in this fastening step, the sheet stack and the plate material 45 are arranged to face each other so that the sheet stack is located on the first annular body 80 side and the plate material 45 is located on the second annular body 85 side). More specifically, the following operations 1 and 2 are performed in order to fasten the first jig 41 and the second jig 42, and the measuring device 40 is assembled.

[0301] Step 1: The ferrule gasket 47, the sheet stack, and the plate material 45 are positioned between the first annular body 80 and the second annular body 85 so that the ferrule gasket 47, the sheet stack, and the plate material 45 are positioned in that order from the first annular body 80 side to the second annular body 85 side. Step 2: The first jig 41 and the second jig 42 are fastened together using a ferrule clamp 43 to assemble the measuring device 40.

[0302] Next, the orientation of the measuring device 40 is adjusted so that the first jig 41 is on the upper side and the second jig 42 is on the lower side, and a filling step is performed to fill the internal space of the first annular body 80 with the liquid L. Liquid L is an aqueous solution of ion-exchanged water containing ethanol and sodium chloride. The color is generated by adding a color solution.

[0303] In the above fastening step, as shown in FIG. 22, the first jig 41 and the second jig 42 may be fastened by the clamp 43 in a state in which the nonwoven fabric 70 and the resin film 71 are sandwiched between the sheet stack and the plate material 45. The nonwoven fabric 70 is disposed so as to contact the sheet stack and is provided to support the sheet stack. For example, Eltas manufactured by Asahi Kasei Corporation can be used as the nonwoven fabric 70. The resin film 71 is disposed so as to contact the plate material 45 and is provided to suppress creep. For example, Lumirror (registered trademark) manufactured by Toray can be used as the resin film 71. Note that a polyester-based film is preferable as the material of the resin film, and specifically, a polyethylene terephthalate (PET) film is preferable.

[0304] After the above fastening process, the legs are placed under constant temperature and humidity conditions of 50±15% humidity and 25±3°C room temperature. An application step is carried out in which air is continuously supplied from the regulator 44 to the internal space of the first annular body 80, thereby continuously applying water pressure from the liquid L to the sheet laminate. At this time, the valve of the regulator 44 is operated to adjust the amount of air supplied to the internal space of the first annular body 80, so that a water pressure of 0.02 MPa or more and 1 MPa or less is applied to the sheet laminate for 50 days. When the liquid L passes through any part of the sheet laminate due to the application of water pressure, the liquid L passes through the through hole 60 located opposite the part that passed through. Then, the plate material The coloring of the liquid L can be confirmed from the side 45 (see FIG. 23 described later). By setting the water pressure to 1 MPa or less, it is possible to prevent the sheet laminate from being torn. In addition, at the beginning of the application process, it is preferable to set the initial water pressure to 0.02 MPa and to increase the water pressure at a rate of 0.1 MPa / min. It is nice.

[0305] After the above-mentioned application step, a measurement step is carried out in which the number of through holes 60 through which the liquid L has passed (i.e., the number of through holes 60 in front of the part of the sheet laminate through which the liquid L has passed) is measured as the leakage degree (degree of water leakage) of the sheet laminate by visually checking the measuring device 40 from the side of the second jig 42. FIG. 23 shows the state of the plate material 45 when the measurement step is carried out (in FIG. 23, the colored areas of the sheet laminate are shown by dotted lines). For example, the through holes 60A, 60B, and 60C shown in FIG. 23 are through holes 60 in front of the colored part of the sheet laminate, and therefore are identified as the through holes 60 through which the liquid L has passed. On the other hand, the through holes 60A, 60B, and 60C shown in FIG. 23 are identified as the through holes 60 through which the liquid L has passed. The holes 60D and 60E are identified as through-holes 60 through which the liquid L has not passed, since the portions of the sheet stack behind them are not colored.

[0306] (Leakage rate of laminated sheet) In this embodiment, a sheet laminate having a leakage degree (the number of through holes 60 through which water has passed) of 50 or less measured in the above measurement process is applied to a wastewater treatment device (i.e., a sheet laminate having a leakage degree of 50 or less is provided to a gas supply body, and the gas supply body is installed inside a wastewater treatment tank). The sheet laminate having the leakage degree of 50 or less suppresses leakage over almost the entire range (a range of 94% or more) even when a water pressure of 0.02 MPa or more and 1 MPa or less is continuously applied for a long period of 50 days (94% is a value obtained by calculating (1-50 / 813) x 100%). Therefore, by applying the above sheet laminate to a wastewater treatment device, the wastewater treatment device can maintain purification performance for a long period of time. In addition, according to the above measurement device 40 and measurement method, water pressure by the liquid L can be applied to the sheet laminate by supplying air to the internal space of the first annular body 80. Therefore, the supply of air for a long period of time can be performed. This allows water pressure to be applied to the sheet laminate for a long period of time, making it possible to evaluate the long-term water leakage of the sheet laminate.

[0307] In order to form a sheet laminate having a leak rate of 50 or less, it is preferable to use the materials for the substrate 211, the gas-permeable non-porous layer 212, and the microorganism support layer 213 shown in the first embodiment.

[0308] Even if the sheet laminate does not include the substrate 211, the gas permeable non-porous layer 212, or the microorganism support layer 213, it is possible to manufacture a sheet laminate in which the number of through holes 60 through which water passed is 50 or less in the above-mentioned water pressure application test, as long as the substrate 211 or the gas permeable non-porous layer 212 is present. Therefore, the substrate 211, the gas permeable non-porous layer 212, or the microorganism support layer 213 are not necessarily required, and may be omitted from the sheet laminate (in other words, the sheet laminate only needs to include at least the substrate 211, the gas permeable non-porous layer 212, or the microorganism support layer 213).

[0309] (Short-term pressure resistance of sheet laminate) Furthermore, the sheet laminate preferably has a short-term pressure resistance of 0.1 MPa or more, and more preferably 0.2 MPa or more, as measured by the following short-term leak performance test.

[0310] (Short-term leak performance test) The short-term leak performance test mainly follows JIS L 1092:2009, 7.1.2 Water resistance test (static The short-term withstand pressure is measured by a method that is a partial modification of the B method (high water pressure method) of the I method. The pressure is the value on the pressure gauge when water first appears through the test piece. Below are the differences from the water resistance test (hydrostatic pressure method).

[0311] A support nonwoven fabric (Unitika Marix 82607WSO) is placed on the opposite side of the sheet laminate to which water pressure is applied. This makes it easier to see the water coming through the test piece. The water used in the test is ion-exchanged water with Allura Red added as a coloring solution. The rate at which the water pressure is increased is 0.1 MPa per minute.

[0312] (Oxygen supply rate of sheet laminate) The sheet laminate also has an oxygen supply rate Q (gO2 / m) determined in the oxygen supply performance test shown in embodiment 1. 2 / day) is 25g / m 2 / day or more, and 26 g / m 2 / day or more is more preferable, and 27 g / m 2 / day or more is more preferable.

[0313] (Organic matter removal rate of laminated sheet) Moreover, the sheet laminate has an organic matter removal rate R determined from the purification treatment performance test shown in embodiment 1 of preferably 80% or more, more preferably 81% or more, and even more preferably 82% or more. The organic matter removal rate R includes an organic matter removal rate R1 determined from the CODCr concentration A mg / L after 28 days and the CODCr concentration B mg / L after 31 days, and an organic matter removal rate R2 determined from the CODCr concentration A mg / L after 56 days and the CODCr concentration B mg / L after 59 days. It is preferable that both of these organic matter removal rates R1 and R2 are 80% or more.

[0314] [Example] The inventors of the present application conducted the above-mentioned water pressure application test, short-term leak performance test, oxygen supply performance test, and purification treatment performance test on various sheet laminates. Table 7 below shows the materials used to form each sheet laminate and the results of each test.

[0315] [Table 7]

[0316] Examples 31 to 35 shown in Table 7 are sheet laminates whose leakage degrees measured in the water pressure application test were 50 or less. Comparative Examples 10 to 13 shown in Table 7 are sheet laminates whose leakage degrees measured in the water pressure application test were over 50.

[0317] The sheet laminate of Example 31 was composed only of a substrate 211, and as the substrate 211, a microporous membrane included in Celpore NWE08 manufactured by Sumika Sekisui Film Co., Ltd. was used.

[0318] The sheet laminate of Example 32 is a laminate of a substrate 211 and a microorganism support layer 213. A microporous membrane included in Celpore NW07H manufactured by Sumika Sekisui Film Co., Ltd. was used as the substrate 211, and a polyolefin nonwoven fabric included in the above Celpore NW07H was used as the microorganism support layer 213 (Celpore NW07H has a three-layer structure of a nonwoven fabric, a polyolefin microporous membrane, and a nonwoven fabric, of which the polyolefin microporous membrane was used as the substrate 211, and one of the nonwoven fabrics was used as the microorganism support layer 213).

[0319] The sheet laminate of Example 33 is composed of a substrate 211, a gas-permeable non-porous layer 212, and a microorganism support layer 213. The substrate 211 is made of the microporous membrane contained in the above-mentioned Celpore NW07H manufactured by Sumika Sekisui Film Co., Ltd., and the microorganism support layer 213 is made of the polyolefin nonwoven fabric contained in the above-mentioned Celpore NW07H. (Note that the microporous membrane and polyolefin nonwoven fabric The laminate is defined as a Celpore NW07H semi-finished product. A gas-permeable non-porous layer 212 is formed on the microporous membrane. Silicone resin was applied to the silicone resin coating surface at a thickness of 40 μm, and the silicone resin coating surface was coated with an engraving machine manufactured by Asahi Kasei Corporation. Rutas (40g / m 2 ) was laminated. During the water pressure application test, as shown in Fig. 15, a nonwoven fabric 70 having an outer diameter of 155 mm and a PET film 71 were sandwiched between the sheet laminate and plate material 45, so that the nonwoven fabric 70 was in contact with the sheet laminate of Example 33 and the PET film 71 was in contact with plate material 45. The nonwoven fabric 70 was Eltas manufactured by Asahi Kasei Corporation. The PET film 71 was Lumirror (T60-100 µm) manufactured by Toray Industries, Inc.

[0320] The sheet laminate of Example 34 includes a substrate 211 and a gas-permeable non-porous layer 212. Tyvek House Wrap (moisture-permeable, waterproof sheet (sheet for use as a base for exterior walls of houses, soft type) manufactured by DuPont was used as the substrate 211. A mixed solution of a methylvinyl silicone resin, a crosslinking agent, a platinum catalyst, etc. was applied onto the substrate 211 using a bar coater, and the mixture was then left to stand for 1 hour in an atmosphere at 70° C., forming a 40 μm-thick gas-permeable non-porous layer on the substrate 211. A body-permeable non-porous layer 212 is laminated thereon.

[0321] The sheet laminate of Example 35 is a laminate in which a substrate 211, a gas-permeable non-porous layer 212, and a microorganism support layer 213 are laminated in this order. The substrate 211 is a microporous membrane included in Celpore NW07H manufactured by Sumika Sekisui Film Co., Ltd. Then, a mixed solution of a methylvinyl silicone resin, a crosslinking agent, a platinum catalyst, etc. is applied onto the substrate 211 using a bar coater, and then the mixture is left to stand for 1 hour in an atmosphere at 70°C, thereby forming a gas-permeable non-porous layer 212 having a thickness of 40 μm on the substrate. A PET sheet having a thickness of 0.5 mm was then laminated on the gas-permeable non-porous layer 212 as the microorganism support layer 213. The PET sheet had a plurality of perforations having a diameter of 2 mm formed at a pitch of 5 mm.

[0322] The sheet laminate of Comparative Example 10 was a semi-finished product of Celpore NW07H manufactured by Sumika Sekisui Film Co., Ltd. The specimen after immersion was used.

[0323] The sheet laminate of Comparative Example 11 was Tyvek House Wrap (moisture-permeable, waterproof sheet (sheet for housing exterior wall base, soft type) manufactured by DuPont.

[0324] The sheet laminate of Comparative Example 12 was a Tyvek flashing sheet (moisture-permeable drainage sheet (sheet for use as a base for exterior walls of houses, soft type) manufactured by DuPont.

[0325] The sheet laminate of Comparative Example 13 was prepared by applying a water repellent spray to a nonwoven fabric. Eltas manufactured by Asahi Kasei Corporation was used as the nonwoven fabric.

[0326] (Leak level confirmed by water pressure application test) In the water pressure application test, as shown in the above embodiment, a water pressure of 0.02 MPa or more and 1 MPa or less was applied to the sheet laminate from the opposite side of the plate material 45 for 50 days by the liquid L, and the number of through holes 60 through which the liquid L passed was measured as the leakage degree (degree of water leakage) of the sheet laminate. As a result, as shown in Table 7, in Examples 31 to 33, the leakage degree was 50 or less, and in Comparative Examples 10 to 13, the leakage degree exceeded 50. In addition, in Examples 31, 33, and 35, a water pressure of 0.02 MPa or more and 1 MPa or less was applied for 200 days, and in Examples 31, 33, and 35, the leakage degree was 40 or less throughout the entire 200-day period.

[0327] (Regarding short-term pressure resistance confirmed in short-term leak performance tests) It was confirmed that all of Examples 31 to 35 had a short-term pressure resistance within the preferred range (0.1 MPa or more). In particular, Examples 31, 33, 34, and 35 had a short-term pressure resistance of 0.4 MPa or more, and were confirmed to have high short-term pressure resistance. Comparative Example 10 had a short-term pressure resistance of 0.4 MPa or more, similar to Examples 31, 33, 34, and 35, but the degree of long-term water leakage was not observed. The leak degree indicated was 200. This confirmed that even if the sheet laminate does not leak water in the short term, water may leak from the sheet laminate if water pressure is continuously applied to the sheet laminate for a long period of time.

[0328] (Oxygen supply rate confirmed in oxygen supply performance test) In Examples 31 to 34, the oxygen supply rate was within the preferred range (25 g / m 2 / day or more) The oxygen supply rate in Example 35 was 15 g / m 2 / day, but this is It is believed that in Example 35, the gas-permeable non-porous layer 212 containing silicone and the microorganism support layer 213 made of a PET sheet were in close contact with each other, blocking the oxygen permeation passage.

[0329] (Regarding the organic matter removal rate R confirmed in purification treatment performance tests) In Comparative Examples 11 to 13, in which the leakage degree exceeded 50, the organic matter removal rate R1 calculated from the CODCr concentrations A and B after 28 and 31 days was 90%, but the organic matter removal rate R2 calculated from the CODCr concentrations A and B after 56 and 59 days was 30% or 0%, and the removal rate R was significantly reduced. In contrast, in Examples 31 to 34, in which the leakage degree was 50 or less, both the removal rate R1 and the removal rate R2 were 90% or more. In Example 35, the organic matter removal rates R1 and R2 were low at 60% and 50%, but the reduction in the removal rate R was suppressed to 10% (= 60% - 50%). From the above, it was confirmed that the organic matter removal rate R can be maintained at a nearly constant value for a long period of time by using a sheet laminate capable of preventing water leakage for a long period of time.

[0330] (Embodiment 6) Next, a sixth embodiment of the present invention will be described.

[0331] (Gas supplier) 24 is a schematic diagram showing a gas supplier 90 of embodiment 6. The gas supplier 90 of embodiment 6 is a gas supplier for water treatment having one gas sending layer 91 and a sheet laminate 92. The sheet laminate 92 includes one or more gas permeable non-porous layers, and the gas supplier 90 has a leak parameter X, expressed by the following formula (10), of 1.9 or more when immersed to the sheet effective height H (m).

[0332] [Formula 10] X = E / (P × A) E: Elastic parameter of the sheet laminate 92 (N / 10 mm) P: Water pressure applied to the sheet (kPa), expressed by the relation P = 10 x H, where H is the effective sheet height (m). A: Diameter of the vent hole on the surface of the gas delivery layer 91 (mm)

[0333] (Leak parameter X) The leak parameter X is 1.9 or more, and more preferably 5 or more. If the leak parameter is less than 1.9, the leak will become large during long-term use. Generally, there is no direct correlation between the elastic parameter and the creep strength. However, as a result of intensive research, it has been found that a gas supplier 90 for water treatment with less leaks over the long term can be obtained by making the leak parameter X calculated using the elastic parameter E a predetermined value or more. In addition, the elastic parameter has the advantage of being easier to measure than the creep strength.

[0334] Generally, creep is more likely to occur when a material is subjected to a large stress. When the maximum water pressure P at the sheet effective height H is large, a large tensile stress is generated in the sheet laminate 92 located above the vent hole on the surface of the gas-transporting layer, and creep is more likely to occur. When the diameter A of the vent hole on the surface of the gas-transporting layer is large, a large tensile stress is generated in the sheet laminate 92. However, the creep phenomenon is likely to occur. In the gas supply body 90 for water treatment, the degree of creep phenomenon varies depending on the balance of E, P, and A. It is possible to suppress the leak phenomenon by making the sheet laminate 92 strong enough to prevent the creep phenomenon, that is, by increasing E to the extent that the effects of P and A do not need to be taken into account, but this will result in over-spec and high costs. In order to increase E, a method of making the sheet laminate 92 thick is often used, but if the sheet laminate 92 is made too thick, gas permeability is impaired and treatment performance is reduced.

[0335] Therefore, by considering an appropriate balance between E, P, and A and setting the leak parameter X to 1.9 or more, it is possible to provide a gas supplier 90 for water treatment that has little leakage even after long-term use, is low cost, and has high treatment performance. In addition, the upper limit value of the leak parameter X is not particularly limited, but from the viewpoint of ensuring treatment performance, it is preferably set to, for example, 2000 or less, and more preferably set to 600 or less.

[0336] In the above formula (12), E is the elastic parameter of the sheet laminate 92, and the elastic parameter can be calculated from a diagram showing the relationship between the test force and strain of the material (hereinafter referred to as the test force-strain diagram). The test force-strain diagram is basically created in accordance with the test method of JIS K7161-1:2014 Plastics - How to determine tensile properties, but a dumbbell-shaped No. 1 test piece is used and the test speed is 100 mm / min. From the above tensile property test, the relationship between the test force (N / 10 mm) and strain is shown in a diagram, and the elastic parameter (N / 10 mm) can be calculated from the slope of the elastic region of the test force-strain diagram according to ASTM D638-03. If the elastic region is not observed, the elastic parameter may be calculated from the method of determining the secant modulus described in ASTM D638-03. The term elastic parameter used in this specification differs from the commonly used elastic modulus (elastic modulus), and is a value obtained by the method defined above and expressed in units of (N / 10 mm).

[0337] The elastic parameter E is preferably 10N / 10mm or more, and more preferably 50N / 10mm or more. If the elastic parameter E is 10N / 10mm or more, the sheet laminate 92 can be easily processed. In particular, when the sheet laminate 92 is processed into a bag shape, the processing is facilitated because the slippage during bonding and fusion is suppressed. Furthermore, the elastic parameter E is more preferably 100N / 10mm or more. If the elastic parameter E is 100N / 10mm or more, the gas-sending layer can be easily installed inside the sheet laminate 92. On the other hand, the elastic parameter E is preferably 1000N / 10mm or less, more preferably 500N / 10mm or less, and even more preferably 350N / 10mm or less. By setting the elastic parameter E to 1000N / 10mm or less, the thickness of the sheet laminate 92 does not become an issue, and sufficient oxygen permeability can be obtained, and as a result, sufficient processing performance can be obtained.

[0338] P is the maximum water pressure (unit: kPa) at the sheet effective height H (m), and is expressed as P = 10 × H. In this specification, the sheet effective height H is defined as the height dimension of the gas supply body 90 or the inner dimension of the laminated bag in the height direction when the gas supply body 90 or the laminated bag is installed in the wastewater treatment device. Therefore, from the viewpoint of cost and installation space, the sheet effective height H is preferably 0.3 m or more, and more preferably 0.5 m or more. On the other hand, in order to prevent compression deformation due to the water pressure of the gas-sending layer, the sheet effective height is preferably 20 m or less, and more preferably 5 m or less. In this specification, the immersion depth, that is, the water depth at which the lowest part of the gas supply body 90 is located when the gas supply body 90 is immersed in the liquid to be treated, is defined as 90% of the sheet effective height.

[0339] A is the diameter of the vent hole present on the surface of the gas-transporting layer 91. The vent hole diameter (hereinafter also simply referred to as the hole diameter) is measured using a vernier caliper, an optical microscope, a digital camera, or the like. If the diameter is less than 5 mm, an image of the vent hole is taken using an optical microscope, and the image of the vent hole obtained can be subjected to image analysis software to obtain the hole diameter using the three-point arc method. If the vent hole is not a nearly perfect circle, the diameter of the largest circle inscribed in the vent hole is measured. At this time, the magnification is determined so that the entire vent hole to be observed is included in the field of view of the image and the hole diameter obtained above is 10% or more of the maximum length of the field of view. If the image obtained is unclear and it is difficult to evaluate the hole diameter using the image analysis described above, the hole diameter is obtained by applying a similar image analysis after appropriately performing binarization processing.

[0340] If the hole diameter is 5 mm or more, the hole diameter is measured using a caliper certified by a Japanese public institution. At this time, if the air hole is approximately a perfect circle, any diameter part may be measured, but if the air hole is not approximately a perfect circle, the part with the diameter of the largest circle inscribed in the air hole is measured. Alternatively, if an image is taken with a digital camera instead of the optical microscope described above, the hole diameter can be obtained in the same manner as above. At this time, a standard scale with a known length is photographed under the same conditions as the image of the air hole, and the length is corrected using the obtained image.

[0341] The above measurement is applied to at least 10 air holes, whether the hole diameter is less than 5 mm or 5 mm or more, and the average of the obtained hole diameters is defined as hole diameter A.

[0342] (Sheet laminate) The sheet laminate 92 (FIG. 24) includes a substrate which is a microporous membrane and a gas-permeable non-porous layer, through which gas (air) can pass but water cannot. A microorganism support layer can be provided on the outer surface of the sheet laminate 92. In this case, the sheet laminate 92 has a function in which, for example, gas passing through the gas-delivery layer 91 is transported to one main surface of the sheet laminate 92, crosses the gas-permeable non-porous layer by diffusion or the like, and reaches the microorganism support layer formed on the outer surface of the sheet laminate 92. The substrate provided on the sheet laminate 92 is a membrane having many fine through-holes provided therein by stretching or solvent extraction during membrane production, and has various functions such as controlling the passage of fluids and adsorbing and fixing substances, and is also called a microporous film. The pore size is preferably 0.01 μm to 50 μm from the viewpoint of preventing defects in the gas-permeable non-porous layer, and more preferably 0.1 μm to 30 μm from the viewpoint of maintaining high strength and gas permeability.

[0343] The thickness of the gas-permeable non-porous layer provided in the sheet laminate 92 is preferably 10 μm or more, more preferably 50 μm or more. By making the thickness of the gas-permeable non-porous layer 10 μm or more, there is an advantage that the elastic parameter can be easily increased. By making the thickness of the gas-permeable non-porous layer 50 μm or more, there is an advantage that the gas-permeable non-porous layer is less likely to be damaged when processing the gas supply body 90 or installing the gas supply body 90 in a wastewater treatment device. On the other hand, the thickness of the gas-permeable non-porous layer is preferably 500 μm or less, more preferably 200 μm or less. By making the thickness of the gas-permeable non-porous layer 500 μm or less, there is an advantage that high oxygen permeability can be easily obtained.

[0344] The thickness of the gas-permeable non-porous layer is measured in accordance with JIS1913:2010 General Nonwoven Fabric Test Method 6.1 Thickness Measurement Method. It can be measured based on the

[0345] (Gas sending layer) The gas-sending layer 91 (FIG. 24) is a layer that ensures a gas flow path and maintains the shape of the gas supply body 90 so that the gas supply body 90 does not deform due to water pressure. There are no particular limitations on the shape of the gas-sending layer, and it is preferable that the gas-sending layer has, for example, a sponge shape, a honeycomb shape, or a cardboard shape. These shapes can be formed by known methods.

[0346] The surface of the gas-delivery layer 91 has vent holes 93 (FIG. 24) with a diameter of A mm. This can be measured by the "measuring pore size distribution by capillary condensation method (perm porosimetry)" shown in embodiment 1. The ventilation holes 93 may or may not penetrate the gas-transporting layer 91. The ventilation holes 93 enable oxygen to be supplied to the microorganisms through the sheet laminate 92.

[0347] The hole diameter A of the ventilation holes 93 in the gas-sending layer 91 is preferably 0.1 mm or more from the viewpoint of reliably forming through holes when processing the ventilation holes, and more preferably 0.5 mm or more from the viewpoint of ensuring the oxygen supply performance to the sheet laminate 92 and improving the organic matter removal performance of the obtained gas supplier 90. There is no particular limit to the upper limit of the hole diameter A, and it is, for example, preferably 100 mm or less, more preferably 30 mm or less.

[0348] The aperture ratio of the ventilation holes 93 on the gas-transporting layer 91 to the area of ​​one side of the gas-transporting layer 91 is preferably set to be within the range of 1% to 90%, and more preferably within the range of 1% to 80%. An aperture ratio of 1% or more can supply oxygen to microorganisms in the wastewater and ensure the wastewater treatment capacity. On the other hand, an aperture ratio of 90% or less can reliably support the sheet laminate 92 and suppress deformation of the sheet laminate 92 caused by water pressure, so that the movement of gas in the gas-transporting layer 91 is not hindered and the wastewater treatment capacity can be favorably obtained. Here, in the part of the gas supply body 90 that contacts the wastewater, the outer surface area S1 (m 2 ), total area of ​​ventilation holes S2 (m 2 ), the opening rate P (%) of the ventilation hole is calculated by the following relational expression (11).

[0349] [Formula 11] P = S2 / S1 x 100

[0350] The material constituting the gas-sending layer 91 is not particularly limited, and examples thereof include one or more materials selected from the group consisting of paper, ceramic, aluminum, iron, stainless steel, aluminum, plastic (polyolefin resin, polystyrene resin, polyester resin, polyvinyl chloride resin, acrylic resin, urethane resin, epoxy resin, polyamide resin, methyl cellulose resin, ethyl cellulose resin, polyvinyl alcohol resin, vinyl acetate resin, phenol resin, fluororesin, and polyvinyl butyral resin), polycarbonate resin, polyamide resin, melamine resin, and unsaturated polyester resin.

[0351] The gas-delivery layer can be manufactured using the above resin as a material by widely adopting known methods. There is no particular limitation on the method of providing the vent holes, and widely adopting known methods. Specifically, the resin sheet formed can be subjected to a method of rotating a roll having a plurality of needles arranged on its surface, a method of pressing a plate having a plurality of needles or blades arranged on its surface, and a method using NC automatic cutting. Here, in the method using the above roll, the size of the vent holes can be changed by changing the shape of the needles arranged on the roll. Also, larger vent holes can be processed by increasing the angle of the apex of the needle.

[0352] The flexural modulus of the material is preferably 500 MPa or more, and more preferably 1000 MPa or more. With this configuration, even if high water pressure is applied during use of the gas supplier 90, the air holes are unlikely to become large, and as a result, the occurrence of leakage is suppressed. In addition, the flexural modulus of the material is preferably 4500 MPa or less, and more preferably 3000 MPa or less. The flexural modulus of the material may be measured based on the ASTM test method D790.

[0353] The bending strength of the material is preferably 5 MPa or more, and more preferably 10 MPa or more. It is more preferable that the material has a bending strength of 150 MPa or less, and more preferably 100 MPa or less. With such a configuration, the vent hole is unlikely to become large even if high water pressure is applied when the gas supplier 90 is used, and as a result, the occurrence of leakage is suppressed. In addition, the bending strength of the material is preferably 150 MPa or less, and more preferably 100 MPa or less. The bending strength of the material may be measured according to the ASTM test method D790.

[0354] The 24-hour water absorption rate of the material is preferably 0.001 or more, and more preferably 0.005 or more. With this configuration, it is possible to prevent the occurrence of a decrease in strength of the gas supply body 90 due to humidity, and as a result, deformation of the gas supply body 90 is suppressed, and the air vents are less likely to become large. In addition, the 24-hour water absorption rate of the material is preferably 0.6 or less, and more preferably 0.2 or less. The 24-hour water absorption rate of the material may be measured based on ASTM test method 570.

[0355] The thickness of the gas-delivery bed is preferably 1 mm or more, more preferably 3 mm or more, from the viewpoint of supplying sufficient oxygen into the gas-delivery bed, and is preferably 100 mm or less, more preferably 40 mm or less, from the viewpoint of increasing the number of gas suppliers 90 per unit volume of the treatment device and achieving a high treatment speed per unit volume of the treatment device.

[0356] The weight of the gas-transporting layer is 100g / m2 to ensure strength against water pressure. 2 It is preferable that the thickness is 400 g / m or more. 2 In consideration of ease of processing of the gas supply body 90, the basis weight of the gas-sending layer is preferably 5000 g / m 2 It is preferable that the thickness is less than 3000 g / m 2 It is more preferable that:

[0357] (microbial support layer) The gas supply body 90 of the present invention may have a microbial support layer on one or both sides of the gas-permeable, water-impermeable layer.

[0358] The microbial support layer preferably has a structure as a support for supporting microorganisms. Examples of such a support structure include nonwoven fabrics manufactured by airlaid manufacturing, carding manufacturing, stitchbond manufacturing, spunbond manufacturing, spunlace manufacturing, ultrasonic bonding manufacturing, wetlaid manufacturing, and meltblown manufacturing. Other examples include structures such as woven fabrics, knitted fabrics, and porous ceramics. Such structures can be manufactured by widely adopting known methods.

[0359] As the microorganisms used in the microbial support layer, known microorganisms used in the purification treatment of wastewater, etc. can be widely applied. As the method for attaching the microorganisms to the structure as the support, known methods can be widely adopted and are not particularly limited. When the wastewater contains microorganisms, the gas supplier 90 is immersed in the wastewater to attach the microorganisms. When it is necessary or effective to attach the microorganisms before starting operation, specifically, the microbial support layer may be provided by an appropriate method such as applying a microbial preparation or the like to the surface of the microbial support layer using an appropriate solvent and binder as necessary.

[0360] Here, when the microorganism support layer is provided on only one side of the gas-permeable impermeable layer, it is preferable to have a gas supplier 90 having a gas-transporting layer, a gas-permeable impermeable layer, and a microorganism support layer in this order. It is also preferable to provide a mesh, a woven fabric, a nonwoven fabric, a foam, or the like between the gas-transporting layer and the gas-permeable impermeable layer.

[0361] In this case, it is also preferable to provide a gas inlet at the end and to form a bag shape in which the gas delivery layer is disposed inside. The gas inlet is a passage for allowing gas to flow from the outside of the gas supply body 90 to the inside. The gas inlet may be a gas inlet passage for supplying gas to the gas-delivery layer 91 in the gas supply body 90 by using power. Furthermore, it is also preferable to use a bag-shaped member formed by laminating sheet materials that are permeable to gas but impermeable to liquid as the layer covering the surface of the gas-delivery layer 91. By adopting such a structure, the surface of the gas-delivery layer 91 can be covered with the gas-permeable imperforate layer simply by inserting the gas-delivery layer 91 from the opening side of the bag. As a result, when the gas supply body 90 is immersed in liquid, gas can be supplied by permeating from the gas-delivery layer 91 side through the gas-permeable imperforate layer into the liquid without the liquid permeating to the gas-delivery layer 91 side.

[0362] It is also preferred that the gas-permeable non-porous layer is made up of a first gas-permeable non-porous layer and a second gas-permeable non-porous layer. In this case, it is preferred that the gas supply body 90 has a first gas-permeable non-porous layer, a gas-transporting layer, and a second gas-permeable non-porous layer in this order. Furthermore, a microbial support layer may be laminated on the surface of the first gas-permeable non-porous layer opposite the gas-transporting layer, or on the surface of the second gas-permeable non-porous layer opposite the gas-transporting layer, or on both. It is also preferred to provide a mesh, woven fabric, non-woven fabric, foam, or the like between the first or second gas-permeable non-porous layer and the gas-transporting layer, or both.

[0363] The method for laminating the gas-permeable non-porous layer, the gas-transporting layer, and the microbial support layer is not particularly limited, and any known method can be widely used. Specifically, a method using an adhesive, a method using heat fusion, etc. can be used.

[0364] The gas supplier of the present embodiment configured as described above can be suitably used for the treatment of wastewater such as sewage, human waste, and industrial wastewater, and for the purification of first flushes of lake water, river water, groundwater, rainwater, etc. Among these, the gas supplier can be suitably used for wastewater treatment because it can effectively reduce a large amount of energy consumed.

[0365] Hereinafter, the sixth embodiment will be described in more detail based on examples, but the present invention is not limited to these.

[0366] (Opening of vent holes in gas delivery layer) A roll with multiple needles arranged on its surface was rotated on a plastic cardboard, and the plastic cardboard was passed between the roll and a flat surface, thereby forming multiple air holes on the surface of the plastic cardboard.

[0367] (Measurement of the diameter of the ventilation hole) When the hole diameter is 5 mm or more, the hole diameter is measured using a caliper. The existing vent holes were almost perfectly circular, so the diameter was measured. If the hole diameter was less than 5 mm, We used a Keyence VHX-6000 microscope as an optical microscope and observed the vent hole. The image of the vent hole was taken at a magnification where the hole diameter was included in the field of view, and the diameter was obtained by applying the diameter measurement in the normal measurement mode to the obtained image of the vent hole. At this time, the magnification was determined so that the entire vent hole to be observed was included in the field of view, and the hole diameter obtained above was 10% or more of the maximum length of the field of view. The above measurements were applied to 10 vent holes for one sample, and the average value of the obtained hole diameters was taken as the vent hole diameter.

[0368] (Water pressure measurement) The water pressure P (kPa) was calculated from the water depth at the bottom of the sheet gas supply body, i.e., the sheet effective height H (m), using the following formula. The water depth at the bottom was calculated using Tajima Tool Lock-16 L16-55. The measurements were taken. P=10×H

[0369] (Elasticity measurement of laminated sheet) The elastic parameters (elastic modulus) of the sheet laminate were calculated from a diagram showing the relationship between the test force and strain of the material (hereinafter referred to as the test force-strain diagram). The test force-strain diagram was basically created in accordance with the test method of JIS K7161-1:2014 Plastics - Determination of Tensile Properties, but the test specimen was a dumbbell-shaped No. 1, and the test speed was 100 mm / min. The above tensile property test The relationship between the test force (N / 10mm) and strain was plotted on a graph, and the test was performed according to ASTM D638-03. The elastic parameter (N / 10mm) was calculated from the slope of the elastic region of the force-strain curve. The average value of three samples in the production direction (MD) during production of the sheet laminate and the average value of three samples in the direction perpendicular to MD (TD) were calculated, and the smaller of these was adopted as the elastic parameter of the sheet laminate.

[0370] (Example 36) The laminated sheet was made of a 290 μm-thick microporous membrane (Celpore NWE08, manufactured by Sekisui Film Co., Ltd.). A polyester nonwoven fabric was laminated on one side of a polyethylene microporous membrane. The elastic parameter of the sheet laminate was 260 N / 10 mm. A polypropylene corrugated cardboard (thickness 5 mm, basis weight 800 g / m2) manufactured by Yamako Co., Ltd. was used as the gas-sending layer 91. 2 ) was used. A roll with multiple needles arranged on its surface was rotated on this plastic cardboard, and the plastic cardboard was passed between the roll and a flat surface, forming multiple ventilation holes on the surface of the plastic cardboard. The ventilation holes arranged on the surface of the gas-delivery layer had a hole diameter of 2 mm. The obtained gas supply was heat-sealed (sealing temperature 140°C, holding time 1 second, cooling temperature 70°C, sealing width 10 mm) using a handy sealer SM-SHTA210-10W-AC manufactured by Fuji Impulse Co., Ltd. The laminate bag was formed by welding the laminate bag to a thickness of 200 mm and the surface on which the polyester nonwoven fabric was not laminated to the inside. The inner dimensions of the laminate bag were 200 cm high and 90 cm wide. The water pressure applied to the sheet laminate was 20 kPa. The leak parameter was 6.5. The wastewater treatment device was operated under these conditions for two months to evaluate the leak property. If 10% or more of the depth length of the laminate bag immersed in the wastewater was submerged due to leakage, it was deemed that there was a problem with the leak property and was rated as ×. If the submersion of the laminate bag due to leakage was less than 10% of the depth length of the laminate bag immersed in the wastewater, it was deemed that there was no problem with the leak property and was rated as ○ (Table 8). The amount of water accumulated in the sheet laminate bag was very small, and there was no problem with the leak property.

[0371] (Example 37) The laminate bag of Example 37 was obtained in the same manner as in Example 36, except that the shape of the needles arranged on the roll was adjusted to a value of 5 mm for the hole diameter of the air hole on the surface of the gas-delivery layer, and the inner dimensions of the laminate bag were 90 cm in height and 60 cm in width.

[0372] (Example 38) The laminated sheet was made of a 160 μm-thick microporous membrane (Celpore NW07H, manufactured by Sekisui Film Co., Ltd.). The elasticity parameter of the laminated sheet was 188N / 10mm. The gas supply was heat-sealed using a Fuji Impulse handy sealer SM-SHTA210-10W-AC. A laminate bag was formed by welding (welding temperature 180°C, holding time 1 second, cooling temperature 90°C, fusion width 10 mm). The inner dimensions of the laminate bag were 50 cm in height and 60 cm in width. A polyvinyl chloride resin corrugated sheet (hard PVC corrugated sheet, slate small wave, pitch about 63 mm, valley depth 18 mm) manufactured by Takiron C.I. was used as a gas-sending layer with ventilation holes, and a polypropylene mesh manufactured by SEFAR, PP18-1000 (mesh opening 1 mm, thread diameter 500 μm, 17 mesh) was laminated to obtain a laminate bag.

[0373] (Example 39) Instead of the polypropylene mesh made by SEFAR, we used Trical Net (H03, mesh pitch 13x13mm) made by Takiron C.I. The inner dimensions of the laminated bag are 100cm high and 6cm wide. A laminate bag of Example 39 was obtained in the same manner as in Example 38, except that the thickness was set to 0 cm.

[0374] (Example 40) The laminate bag of Example 40 was obtained in the same manner as in Example 36, except that the shape of the needles arranged on the roll was adjusted so that the diameter of the vent holes on the surface of the gas-transporting layer was 0.08 mm.

[0375] (Example 41) The sheet laminate is made of Sekisui Film's Celpore NW07H, and the side that comes into contact with the water to be treated is Shin-Etsu An addition reaction curing type silicone resin compound (KR-3700) manufactured by Silicone Co., Ltd. was applied using a bar coater, and then the resin was formed on the porous membrane by leaving the membrane to stand for 1 hour in an atmosphere of 70°C. The silicone resin had a weight per unit area of ​​40 g / m2 after curing. 2 The thickness of the sheet laminate composed of the microbial support layer, the porous membrane, and the resin layer was 190 μm, and the elastic parameter was 190 N / 10 mm. A laminate bag was produced in the same manner as in Example 36, except that the conditions were a fusion temperature of 180° C., a holding time of 1 second, a cooling temperature of 90° C., and a fusion width of 10 mm.

[0376] (Example 42) A laminate bag was obtained in the same manner as in Example 37, except that a polyester nonwoven fabric (Volance 7217P, manufactured by Toyobo Co., Ltd., thickness 0.9 mm, basis weight 215 g / m2) was further laminated on the area other than the heat-sealed portion of the sheet laminate, i.e., on the inner surface of the laminate bag. The elastic parameter of the sheet laminate (a laminate of a microporous membrane and a polyester nonwoven fabric) was 972 N / 10 mm.

[0377] (Comparative Example 14) A laminate bag was obtained in the same manner as in Example 37, except that a polyvinyl chloride resin corrugated sheet (hard polyvinyl chloride corrugated sheet, slate small wave, pitch about 63 mm, valley depth 18 mm) manufactured by Takiron C.I. was used alone as the gas-transporting layer with a vent hole. The hole diameter of the vent hole arranged on the surface of the gas-transporting layer was 60 mm. The leak parameter was 0.5. After operating the wastewater treatment device under these conditions for two months, the amount of water accumulated in the sheet laminate bag was 10% or more of the depth direction length of the laminate bag immersed in the wastewater.

[0378] Comparative Example 15 A laminate bag was obtained in the same manner as in Example 38, except that a polyvinyl chloride resin corrugated sheet (hard polyvinyl chloride corrugated sheet, slate corrugated sheet, pitch about 63 mm, valley depth 18 mm) manufactured by Takiron C.I. was used alone as the gas-transporting layer with a vent hole. The vent hole arranged on the surface of the gas-transporting layer had a hole diameter of 60 mm.

[0379] Comparative Example 16 The same procedure as in Example 36 was repeated, except that a polyvinyl chloride resin corrugated sheet (hard polyvinyl chloride, slate corrugation, pitch approx. 63 mm, valley depth 18 mm) manufactured by Takiron C.I. and a Trical Net (H06, mesh pitch 25 mm x 25 mm) manufactured by Takiron C.I. were used as the gas-transporting layer having ventilation holes. In the same manner, a laminate bag of Comparative Example 16 was obtained.

[0380] Comparative Example 17 The gas-sending layer with ventilation holes was made of a polycarbonate resin corrugated sheet manufactured by Japan Polyester Co., Ltd. (polycarbonate corrugated sheet, slate large wave, pitch about 130 mm, valley depth 36 mm). In the same manner as in Comparative Example 15, a laminate bag of Comparative Example 17 was obtained.

[0381] [Table 8] [Explanation of symbols]

[0382] 10,80,90,110 Gas supply 21,81,92 Sheet stack 50 Wastewater treatment equipment 52 Supplier Unit 211 Base material 212 Gas-permeable non-porous layer 213 Microbial support layer 214 Biofilm W Wastewater

Claims

1. A gas supplier used in a wastewater treatment device that purifies wastewater by utilizing the action of microorganisms in the wastewater, A sheet laminate including a substrate and a gas-permeable non-porous layer; a gas-transporting layer comprising at least one of a honeycomb structure or a mesh structure, and a hollow plate-shaped member; the substrate is a microporous membrane, The gas delivery layer is a gas supplier disposed in the space formed by the sheet stack.

2. 2. The gas supplier according to claim 1, wherein the 24-hour water absorption rate of the gas-sending layer is 0.001 or more and 0.6 or less.

3. 3. The gas supplier according to claim 1, wherein the gas-sending layer has a thickness of 1 mm to 40 mm.

4. The gas-sending layer has a weight per unit area of ​​100 g / m 2 More than 3000 / m 2 3. The gas supplier according to claim 1, wherein:

5. 3. The gas supplier according to claim 1, wherein the gas-sending layer has a vent hole on a surface thereof, the vent hole having a diameter of 0.5 mm to 100 mm.

6. A gas supplier as described in claim 1 or 2, characterized in that the gas delivery layer has air holes on its surface, and the opening rate of the air holes relative to the area of ​​one side of the gas delivery layer is within the range of 1% to 80%.

7. 3. The gas supplier according to claim 1 or 2, wherein the material of the gas-sending layer is at least one selected from the group consisting of paper, ceramic, aluminum, iron, stainless steel, aluminum, polyolefin resin, polystyrene resin, polyester resin, polyvinyl chloride resin, acrylic resin, urethane resin, epoxy resin, polyamide resin, methyl cellulose resin, ethyl cellulose resin, polyvinyl alcohol resin, vinyl acetate resin, phenol resin, fluororesin, polyvinyl butyral resin, polycarbonate resin, polyamide resin, melamine resin, and unsaturated polyester resin.

8. 3. The gas supplier according to claim 1, wherein the material of the gas-sending layer has a flexural modulus of elasticity of 500 MPa or more and 4500 MPa or less.

Citation Information

Patent Citations

  • Layered sheet for gas supply in water treatment

    JP2005511303A

  • Biological treatment system, and biological treatment method

    JP2011189261A

  • Non-powered wastewater treatment method

    JP3743771B2

  • Layered sheet for gas supply in water treatment

    JP4680504B2

  • Electrode structure and microbial fuel cell

    WO2016166956A1